Polyimide microparticles

JP2022174720A5Pending Publication Date: 2025-04-11XEROX CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022063934
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-11
Filing Date
2022-04-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing additive manufacturing techniques face challenges in using polyimides as feedstocks due to their rigid polymer backbone, making it difficult to produce spherical particles of the desired size and morphology suitable for selective laser sintering (SLS), which are essential for better powder flow and mechanical properties.

Method used

A method involving the synthesis of polyimide microparticles through a combination of diamine and dianhydride in a high-boiling solvent, followed by emulsification and polymerization to form poly(amic acid) and then polyimide microparticles, allowing control over particle size and morphology, including porous structures suitable for SLS.

Benefits of technology

The method produces polyimide microparticles with thermoplastic and semi-crystalline properties, enhancing powder flow and mechanical properties, suitable for SLS processes, and expands their application to catalyst supports, membranes, and other high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide methods for producing modified polyimide microparticles that can be shaped into spherical particles with preferred dimensions for selective laser sintering (SLS).SOLUTION: A method for producing polyimide microparticles may comprise: combining a diamine and a dianhydride in a first dry, high boiling point solvent; reacting the diamine and the dianhydride to produce a mixture comprising poly(amic acid) (PAA) and the first dry, high boiling point solvent; emulsifying the mixture in a matrix fluid that is immiscible with the first dry, high boiling point solvent using an emulsion stabilizer so as to form a precursor emulsion that is an oil-in-oil emulsion; and heating the precursor emulsion during and / or after formation to a temperature sufficient to polymerize the PAA to form the polyimide microparticles.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to polyimide microparticles, including their synthesis and applications. [Background technology]

[0002] Polyimide is a high-performance plastic with excellent heat and chemical resistance. Therefore, polyimide is used in a wide variety of applications, including high-temperature fuel cells, flat panel displays, aerospace applications, insulating coatings, high-temperature adhesives, and many more.

[0003] Three-dimensional printing, also known as additive manufacturing, is increasingly being used to fabricate objects. It is considered a versatile technological platform due to its freeform shapes, rapid prototyping, customized component design, and the creation of precise and complex "unfathomable" architectures at low cost. While additive manufacturing has a wide range of applications, including pharmaceuticals, electronics, automotive, construction, military, and aerospace, the versatility and continuous expansion of its applications are increasing the demand for new raw materials with diverse physicochemical properties to meet market demands.

[0004] Selective laser sintering (SLS), one of the most important additive manufacturing technologies, is a powder-based method that enables very complex parts for 3D printing by being self-supporting, without requiring additional auxiliary or sacrificial materials for the overhang layer. In SLS, as with other powder-based AM technologies, spherical polymer particles are preferred for better powder flow, looser powder filling, and improved layer diffusion. The types of SLS raw materials are far fewer than those used in conventional processing methods such as injection molding. This is because SLS raw materials have a number of specific parameters that must be met to be suitable for the SLS process. In the case of polymer particles, three parameters are: (a) the degree to which the polymer particles exhibit thermoplastic properties, b) the degree to which the polymer exhibits a semi-crystalline form, and (c) the average particle size of about 100 micrometers or less, preferably about 50 micrometers or less.

[0005] The thermoplasticity of polymer particles makes the polymer flexible or moldable, at least on the surface of the particles, allowing adjacent particles to fuse under a laser beam. The degree of semi-crystalline morphology of the polymer particles contributes most to the mechanical properties of the fabricated object. The particle size of the polymer particles allows for better powder flow and powder filling during object fabrication by SLS.

[0006] Polyimides are an interesting class of high-performance polymers due to (a) high chemical resistance, heat resistance, and dimensional stability, (b) low dielectric constant and coefficient of thermal expansion, and (c) excellent mechanical properties. Because of these characteristics, PI is a promising candidate for SLS applications, but there are significant processing challenges to consider when converting polyimides into SLS raw materials.

[0007] Generally, polyimides, especially in the case of aromatic polyimides (aramids), which may also be classified as thermosets, have a rigid polymer backbone. Many attempts have been made to produce melt - processable polyimides, mainly based on the incorporation of flexible long - chain aliphatic monomers or bulky monomers into the chemical structure of polyimides. However, forming spherical particles of a preferred size for SLS can be difficult even for these modified polyimides.

Summary of the Invention

[0008] This disclosure relates to polyimide microparticles, such as the synthesis and uses of polyimide microparticles.

[0009] This specification describes a method that includes mixing a diamine and a dianhydride in a first dry high - boiling solvent, reacting the diamine and the dianhydride to produce a mixture containing poly(amic acid) (PAA) and the first dry high - boiling solvent, using an emulsifying stabilizer to emulsify the mixture in a matrix fluid immiscible with the first dry high - boiling solvent to form a precursor emulsion that is an oil - in - oil type emulsion, and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide microparticles during and / or after formation.

[0010] This specification describes a method that includes mixing a diamine and a dianhydride in a first dry high - boiling solvent, reacting the diamine and the dianhydride to produce a mixture containing PAA and the first dry high - boiling solvent, extracting the PAA from the mixture, dissolving the PAA in a second dry high - boiling solvent to produce a PAA solution, using an emulsifying stabilizer to emulsify the PAA solution in a matrix fluid immiscible with the first dry high - boiling solvent to form a precursor emulsion that is an oil - in - oil type emulsion, and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide microparticles during and / or after formation.

[0011] This specification also describes a method comprising optionally depositing polyimide fine particles (produced by one or both of the methods described above) together with thermoplastic polymer particles (preferably of similar size and shape, but which may be porous or solid) onto a surface (for example, in layers and / or in a specific shape), and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object). [Brief explanation of the drawing]

[0012] The following figures are included to illustrate specific aspects of the disclosure and should not be seen as exclusive. The disclosed subject matter can be substantially modified, altered, combined, and equivalent in form and function as can be conceived by those skilled in the art who are interested in the disclosure.

[0013] [Figure 1] This is a non-limiting, illustrative method for producing polyimide particles, which is an example of the present disclosure.

[0014] [Figure 2] This is a non-limiting, exemplary method, which is another example of the present disclosure for producing polyimide particles.

[0015] [Figure 3] This disclosure describes differential scanning calorimetry (DSC) analysis of polyimide microparticles.

[0016] [Figure 4] These are optical microscope images of the polyimide microparticles of this disclosure.

[0017] [Figure 5A] This is a scanning electron microscopy (SEM) image of the polyimide microparticles of this disclosure. [Figure 5B]This is a scanning electron microscopy (SEM) image of the polyimide microparticles of this disclosure. [Figure 5C] This is a scanning electron microscopy (SEM) image of the polyimide microparticles of this disclosure.

[0018] [Figure 6] These are optical microscope images of the polyamide nanoparticles of this disclosure.

[0019] [Figure 7A] This is an SEM image of the polyimide microparticles of this disclosure. [Figure 7B] This is an SEM image of the polyimide microparticles of this disclosure.

[0020] [Figure 8] This is a histogram obtained from the light scattering of the polyimide nanoparticles of this disclosure.

[0021] [Figure 9A] This is an SEM image of the polyimide microparticles of this disclosure. [Figure 9B] This is an SEM image of the polyimide microparticles of this disclosure. [Figure 9C] This is an SEM image of the polyimide microparticles of this disclosure.

[0022] [Figure 10A] This is a cross-sectional SEM image of the polyimide microparticles of this disclosure. [Figure 10B] This is a cross-sectional SEM image of the polyimide microparticles of this disclosure. [Figure 10C] This is a cross-sectional SEM image of the polyimide microparticles of this disclosure. [Modes for carrying out the invention]

[0023] This disclosure relates to polyimide microparticles, including their synthesis and applications. More specifically, this disclosure includes methods comprising (a) the production of a poly(amidic acid) (PAA) precursor by polycondensation, and (b) oil-in-oil emulsion polymerization of the PAA precursor to polyimide microparticles, as well as compositions resulting from such methods. Advantageously, by controlling the conditions of oil-in-oil emulsion polymerization, it may be possible to adjust the average particle size and particle size span of the produced polyimide microparticles. Furthermore, polyimide microparticles produced by the methods described herein may have thermoplastic and semi-crystalline properties, as well as a size desirable for powder materials in SLS additive manufacturing.

[0024] The polyimide microparticle morphology described herein is porous, which allows the polyimide microparticles to be useful in applications other than SLS additive manufacturing. This morphology is such that the polyimide forms an irregular skeleton similar to that found in sol-gels and / or aerogels. This is in contrast to the more regular skeletons found in open-cell morphology, closed-cell morphology, and topologically ordered porous structures. The porous irregular skeleton morphology may include interconnected flake-like and / or ribbon-like structures (e.g., Figure 7D of the Examples) and / or interconnected solidified polymer molten structures (e.g., Figures 9C and 10B of the Examples). The polyimide microparticle morphology increases the surface area of ​​the microparticles compared to solid microparticles of the same dimensions. When combined with high-temperature stability, the polyimide nanoparticles described herein may be suitable as materials for applications such as catalyst supports, high-surface-area films, column packing materials for chromatography (e.g., gas chromatography and liquid chromatography), separation materials, chromatography supports, adsorbents, low-dielectric excipients, drug delivery, phonics crystals, nanoelectronics, biotechnology, biomedical applications (e.g., tissue growth scaffolds), aerospace materials, pervaporation films, optical devices, sensor materials, and other applications using polymer matrices in composite and / or hybrid materials. Definitions and Test Methods

[0025] As used herein, the term “immiscible” refers to a mixture of two or more components that, when combined, form phases with a solubility of less than 5% by weight of each other at ambient pressure and room temperature, or, if solid at room temperature, at the melting point of the components. For example, polyethylene oxide with a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65°C. Therefore, if a material is liquid at room temperature and the polyethylene oxide has a solubility of less than 5% by weight at 65°C, the polyethylene oxide is immiscible with the material.

[0026] When a polymer is referred to in terms of -mer units (e.g., polyimide monomers), those skilled in the art will understand that the -mer units are polymerized within the polymer.

[0027] As used herein, the term "thermoplastic polymer" refers to a plastic polymer material that reversibly softens and hardens upon heating and cooling. Thermoplastic polymers include thermoplastic elastomers.

[0028] As used herein, the term “elastomer” refers to a copolymer comprising a crystalline “rigid” portion and an amorphous “soft” portion. In the case of polyurethane, the crystalline portion may include a portion of polyurethane containing urethane functionality and optionally selected chain-extending groups, and the soft portion may include, for example, a polyol.

[0029] As used herein, the term "polyurethane" refers to the polymer reaction product between a diisocyanate, a polyol, and an optional chain extender.

[0030] As used herein, the term "oxide" refers to both metallic oxides and non-metallic oxides. For the purposes of this disclosure, silicon is considered a metal.

[0031] As used herein, the term “embedding” with respect to particles (e.g., nanoparticles) and the surface of polymer particles means that the particles extend at least partially onto the surface of the polymer particles such that the polymer is in contact with the nanoparticles to a greater extent than would be possible if the nanoparticles were simply placed on the surface of the polymer particles.

[0032] Hereinafter, D10, D50, D90, and diameter span are primarily used to describe particle size. As used herein, the term "D10" refers to the particle size found in 10% of a particle population (relative to a volume-based distribution unless otherwise specified). As used herein, the terms "D50," "average particle diameter," and "average particle size" refer to the particle size found in 50% of a particle population (relative to a volume-based median mean unless otherwise specified). As used herein, the term "D90" refers to the particle size found in 90% of a particle population (relative to a volume-based distribution unless otherwise specified). As used herein, the terms "particle span," "span," and "span size" when referring to particle size provide an indicator of the extent of the particle size distribution and are calculated as (D90-D10) / D50.

[0033] Particle size and particle size distribution were determined by light scattering techniques using the Malvern MASTERSIZER® 3000. For the light scattering techniques, the control sample consisted of glass beads with diameters ranging from 15 μm to 150 μm, obtained from Malvern Analytical Ltd., under the trademark Quality Audit Standards QAS4002®. Unless otherwise specified, samples were analyzed as dry powders. The analyzed particles were dispersed in air and analyzed using the MASTERSIZER® 3000 with the AERO S® dry powder dispersion module. Particle size was derived using instrument software from a plot of volume density as a function of size.

[0034] When used herein, if sieving is mentioned, the pore / screen size is as described by the USA Standard Sieve (ASTM E11-17).

[0035] As used herein, the term “roundness” in relation to particles refers to how close a particle is to being a perfect sphere. To measure roundness, optical microscope images are taken using flow particle imaging. The perimeter (P) and area (A) of the particle within the microscope image plane are calculated (for example, using a SYSMEX FPIA 3000 particle shape and particle size analyzer available from Malvern Instruments). The roundness of the particle is C EA / P is and in the formula, C EA This is the outer circumference of a circle having an area equivalent to the actual particle area (A). In this specification, roundness is based on three analyses using a SysmexFPIA3000 particle shape and particle size analyzer, analyzing 6,000 to 10,000 particles each time. The reported roundness is the median mean roundness based on the number of particles. In the analysis, a threshold for distinguishing the grayscale level between background pixels and particle pixels (e.g., to compensate for uneven lighting conditions) was set to 90% of the background modal value.

[0036] As used herein, the term “shear force” refers to agitation or similar processes that induce mechanical agitation in a fluid.

[0037] Unless otherwise specified, the melting point of the polymer shall be determined according to ASTM E794-06 (2018) with a heating rate and a cooling rate of 10°C / min.

[0038] Unless otherwise specified, the softening temperature or softening point of a polymer is determined according to ASTM D6090-17. The softening temperature can be measured using a 0.50 g sample at a heating rate of 1 °C / min using a cup-and-ball apparatus available from Mettler-Toledo.

[0039] The angle of repose is a measure of the fluidity of a powder. The angle of repose was determined using Hosokawa Micron's Powder Characteristics Tester PT-R, following ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices".

[0040] Hausner ratio (H r ) is a measure of the fluidity of powders, H r =ρ tap / ρ bulk It is calculated by, in the formula, ρ bulk This is the bulk density according to ASTM D6393-14, and ρ tap This is the tap density according to ASTM D6393-14.

[0041] When used herein, the viscosity of the dispersion medium is the kinematic viscosity at 25°C, measured according to ASTM D445-19, unless otherwise specified. For commercially sourced dispersion mediums (e.g., polydimethylsiloxane oil), the kinematic viscosity data referenced herein were provided by the manufacturer, whether or not they were measured according to the aforementioned ASTM or other standard measurement techniques.

[0042] Unless otherwise specified, the crystallization temperature (°C) is determined according to ASTM D3417. The crystallization temperature is the temperature at which a polymer crystallizes (i.e., solidifies) into a structural form, either naturally or artificially initiated, at which point atoms or molecules become highly organized into crystals. The crystallization temperature can be measured by differential scanning calorimetry (DSC). DSC provides a rapid method for determining the degree of polymer crystallinity based on the heat required to melt the polymer.

[0043] Unless otherwise specified, the degree of crystallinity (%) of a polymer is determined by quantifying the heat associated with the melting (fusion) of the polymer, using the 100% crystallinity standard (ΔH = 98 J / g) for polyimide R-BAPB based on 1,3-bis(3,3'-4,4'-dicarboxyphenoxy)benzene (dianhydride R) and 4,4'-bis(4-aminophenoxy)biphenyl (diamine BAPB) according to ASTM D3417.

[0044] Synthesis and composition of polyimide microparticles

[0045] Generally, the methods herein for producing polyimide microparticles include first synthesizing poly(amidic acid) (PAA) and then thermally polymerizing the PAA (where the PAA is part of the inner phase of an oil-in-oil emulsion) to produce polyimide microparticles.

[0046] Figure 1 is a flowchart illustrating a non-limiting exemplary method 100 for the production of polyimide fine particles as described herein. In this example, the diamine 102 and dianhydride 104 are mixed in a high-boiling solvent 106 (108) and then exposed to polycondensation reaction conditions (110) to react the diamine 102 and dianhydride 104 to form PAA. Generally, polycondensation reactions between diamines and dianhydrides occur at ambient temperature and pressure. Therefore, when the diamine 102 and dianhydride 104 are mixed (108), a polycondensation reaction may occur. To mitigate the reaction occurring during mixing (108), the temperature may be lowered during mixing (e.g., below about -20°C). Therefore, the method may include mixing the diamine 102 and dianhydride 104 (108), and then exposing the diamine 102 and dianhydride 104 to polycondensation reaction conditions (110). Alternatively, the method may include mixing the diamine 102 and dianhydride 104 (108) while exposing them to polycondensation reaction conditions (110). In other words, exposure of the diamine 102 and dianhydride 104 to polycondensation reaction conditions (110) may occur during and / or after mixing the diamine 102 and dianhydride 104 (108).

[0047] Examples of diamines, though not limited to them, include: p-phenyldiamine; ethylenediamine; propylenediamine; trimethylenediamine; diethylenetriamine; triethylenetetramine; hexamethylenediamine; heptamethylenediamine; octamethylenediamine; nonamethylenediamine; decamethylenediamine; 1,12-dodecanediamine; 1,18-octadecanediamine; 3-methylheptamethylenediamine; 4,4-dimethylheptamethylenediamine; 4-methylnonamethylenediamine; 5-methylnonamethylenediamine; 2,5 -Dimethylhexamethylenediamine; 2,5-Dimethylheptamethylenediamine; 2,2-Dimethylpropylenediamine; N-Methylbis(3-aminopropyl)amine; 3-Methoxyhexamethylenediamine; 1,2-Bis(3-aminopropoxy)ethane; Bis(3-aminopropyl)sulfide; Trans-1,4-Cyclohexanediamine; Bis-(4-aminocyclohexyl)methane; m-Phenylenediamine; p-Phenylenediamine; 2,4-Diaminotoluene; 2,6-Diaminotoluene; m-Xylylenediamine; p-Xylylene Diamine; 2-methyl-4,6-diethyl-1,3-phenylene-diamine; 5-methyl-4,6-diethyl-1,3-phenylene-diamine; benzidine; 3,3''-dimethylbenzidine; 3,3''-dimethoxybenzidine; 1,5-diaminonaphthalene; bis(4-aminophenyl)methane; bis(2-chloro-4-amino-3,5-diethylphenyl)methane; bis(4-aminophenyl)propane; 2,4-bis(b-amino-t-butyl)toluene; bis(pb-amino-t-butylphenyl)ether; bis(pb-methyl-o-butylphenyl) Minophenyl)benzene; bis(pb-methyl-o-aminopentyl)benzene; 1,3-diamino-4-isopropylbenzene; bis(4-aminophenyl) sulfide; bis(4-aminophenyl) sulfone; bis(4-aminophenyl) ether; 1,3-bis(3-aminopropyl)tetramethyldisiloxane; 2,3,5,6-tetramethyl(teramethyl)-1,4-phenylenediamine; 2,6-diaminotriptycene; 4,4'-oxydianiline; 3,4'-oxydianiline; 4,4'-diaminodiphenyl sulfone;2,5-dimethyl-1,4-phenylenediamine; 4,4'-methylenedianiline; 5-amino-2-(4-aminobenzene)benzimidazole; 2,2'-dimethylbenzidine; 4,4'-diaminobenzanilide; 2,2'-bis(trifluoromethyl)benzidine; 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane; 1R,2R-diaminocyclohexane; 1,3-diaminoadamantane; bis(aminomethyl)bicyclo[2.2. 1] Heptane; 5-tert-butyldimethylsilylamino-N-tert-butyldimethylsilyl-1,3,3-trimethylcyclohexaneethylamine; 2,5-diamino-2,5-dideoxy-1,4:3,6-dianhydroiditol; 2,5-diamino-2,5-dideoxy-1,4:3,6-dianhydrosorbitol; N,N-bis(3-amino-propyl)-methylamine; ethylenediamine; 1,3-diaminopropane; 1,4-diaminobutane; 1,6-Diaminohexane; poly(propylene glycol)bis(2-aminopropyl ether); 2,2'-dimethyl-4,4'-diaminodicyclohexylmethane; 2,2'-bis(trifluoromethyl)-4,4'-diaminobicyclohexylmethane; 4,4'-methylenebis(cyclohexylamine); 4,4'-hexafluoroisopropyldenbis(cyclohexylamine); 4,4'-methylenebis(2-methylcyclohexylamine); bis(4-aminopropyl ether); (no-3-ethylcyclohexyl)methane; 3,3'-diamino-1,1'-diadamantane; trans-11,12-diamino-9,10-dihydro-9,10-ethanoanthracene; 4,4'-diaminodiphenylethane; 4,4'-(cyclohexane-1,4-diylbis(sulfandiyl))dianiline; 1,4-bis[2-amino-4-(trifluoromethyl)phenyl]piperazine; 4,4'-diamino-α-truxillate dimethyl, 4',4''-[(perfluorocyclobutane-1,2-diyl)bis(oxy)]bis((1,1'-biphenyl)-4-amine); 5,5'-isopropylidenebis(2-furfurylamine), 1,1-bis(4-aminophenyl)cyclohexane;1,1-bis(4-aminophenyl)-4-methylcyclohexane; 1,1-bis(4-aminophenyl)-3,3,5-trimethylcyclohexane; 2,2-bis(4-aminophenyl)norbornane; 1,1-bis[4-(2-trifluoromethyl-4-amino-phenoxy)phenyl]-4-tert-butylcyclohexane; 3,3-bis(4-aminophenyl)quinacrylidine; (+)-cis-1,3-bis(4-amino-2(trifluoromethyl)phenoxylmethylene)-1,2,2-trimethylcyclopentane; 1,3-bis (4-aminophenoxymethylene)-1,2,2-trimethylclopentane; 1,4:3,6-dianhydro-2,5-di-O-(4-aminophenyl)-D-mannitol; 1,4:3,6-dianhydro-2,5-di-O-(4-aminophenyl)-D-sorbitol; 2,5-bis(2-trifluoromethyl-4-amino-phenoxy)-1,4:3,6-dianhydrosorbitol; 2,5-bis(2-methyl-4-amino-phenoxy)-1,4:3,6-dianhydrosorbitol; 1,6-bis(4-aminophenyl)dia Mantine; 4,9-bis(4-aminophenyl)diamantine; (5R,11R)-6H,12H-5,11-methanodibenzo[b,f][1,5]diazosin-2,8-diamine; (5S,11S)-6H,12H-5,11-methanodibenzo[b,f][1,5]diazosin-2,8-diamine; 4,10-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazosin-2,8-diamine; 4,10-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazosin-3,9-diamine ;2,8-dibromo-1,4,7,10-tetramethyl-3,9-diamino-6,12-dihydro-5,11-methanodibenzo[b,f][1,5]diazosine;2,4,8,10-tetramethyl-1,7-diamino-6,12-dihydro-5,11-methanodibenzo[b,f][1,5]diazosine;2,8-diamino-1,3,7,9-tetramethyl-6H,12H-5,11-methanodibenzo-[b,f][1,5]diazosine;1,7-diamino-6H,12H-5,11-methanodibenzo[1,5]diazosine-2,8-diol;3,3,3',3'-Tetramethyl-1,1'-Spirobisindan-5,5'-Diamino-6,6'-Diol,5(6),5'(6')-Diamino-3,3,3',3'-Tetramethyl-1,1'-Spirobisindan;6,6'-Bis-[2''-Trifluoromethyl4''-(4'''-Aminophenyl)phenoxy]-3,3,3',3'-Tetramethyl-1,1'-Spirobisindan;4,4'-((3,3,3',3'-Tetramethyl-2,2',3,3' -Tetrahydro-1,1'-spirobio[indene]-6,6'-diyl)bis(oxy))bis(2-methoxyaniline); 3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobio[cyclopenta[b]phenazine]-7,7'-diamine; 1-(4-aminophenyl)-5(6)-aminoindan; 4'-[4-[6-[[4'-amino-3-(trifluoromethyl)[1,1'-biphenyl]-4-yl]oxy]-2,3-dihydroxy [Dro-1,3,3-trimethyl-1H-inden-1-yl]phenoxy]-3'-(trifluoromethyl)-[1,1'-biphenyl]-4-amine; 2,6(7)-diamino-9,10-dimethyl-9,10-dihydro-9,10-ethanoanthracene; 2,8-dimethyl-3,9-diamino-5,6,11,12-tetrahydro-5,11-methanodibenzo[a,e][8]anulene; spiro-(adamantan-2,9'(2',7'-diamino)-fluorene),2 Examples include 2-bis(3-amino-4-hydroxyphenyl)adamantine; 2,2-bis(4-aminophenyl)adamantine; 1,3-bis[4-(4-aminophenoxy)phenyl]adamantine; trans-di(aminobenzo)-18-crown-6,2,2'-dimethyl-4,4'-diaminobiphenyl, 4,9-dioxa-1,12-dodecanediamine; 4,7,10-trioxa-1,13-tridecanediamine, etc.; and any combination thereof.

[0048] Examples of dianhydrides include, but are not limited to, linear dianhydrides, aromatic dianhydrides, and combinations of linear and aromatic dianhydrides. Examples of dianhydrides include, but are not limited to, pyromelitic acid dianhydrides, 2,2-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl ether dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfone Dianhydride; 2,2-bis(4-(2,3-dicarboxyphenoxy)phenyl)propane dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenyl ether dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)benzophenone dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenyl sulfone dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3 ,4-dicarboxyphenoxy)diphenyl-2,2-propane dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenyl ether dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)benzophenone dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3 ,4-Dicarboxyphenoxy)diphenylsulfone dianhydride; 1,2,4,5-Benzenetatracarboxylic acid dianhydride; 1S,2R,4S,5R-Cyclohexanetetracarboxylic acid dianhydride; 1S,2S,4R,5R-Cyclohexanetetracarboxylic acid dianhydride; 1R,2S,4S,5R-Cyclohexanetetracarboxylic acid dianhydride; Bicyclo[2.2.2]octane-2-endo,3-endo,5-exo,6-exo-tetracarboxylic acid 2,3:5,6-dianhydride; Bicyclo[2.2.2] Octane-2-exo,3-exo,5-exo,6-exo-2,3:5,6-dianhydride, cis-1,2,3,4-cyclohexanetetracarboxylic acid dianhydride; trans-1,2,3,4-cyclohexanetetracarboxylic acid dianhydride; bicyclo[2.2.1]heptane-2-endo,3-endo,5-exo,6-exo-tetracarboxylic acid 2:3,5:6-dianhydride; bicyclo[2.2.l]heptane-2-exo, 3-Exo,5-Exo,6-Exo-tetracarboxylic acid 2:3,5:6-dianhydride; (4arH,8acH)-Decahydro-1t,4t:5c,8c-Dimethanonaphthalene-2c,3c,6c,7c-Tetracarboxylic acid 2,3:6,7-dianhydride; (4arH,8acH)-Decahydro-1t,4t:5c,8c-Dimethano-naphthalene-2t,3t,6c,7c-Tetracarboxylic acid 2,3:6,7-dianhydride;rel[1S ,5R,6R]-3-oxabicyclo[3.2.1]octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione),bicyclo[2.2.1]heptane-2-exo,3-exo,5-exo-tricarboxyl-5-endo-acetic acid dianhydride;bicyclo[2.2.1]heptane-2-exo,3-exo,5-endo-tricarboxyl-5-exo-acetic acid anhydride;1,2,3,4-cyclobuta tetracarboxylic dianhydride; butane-1,2,3,4-tetracarboxylic dianhydride; bicyclo-[2.2.2]octo-7-ene-2-exo,3-exo,5-exo,6-exo-2,3:5,6-dianhydride; 1,8-dimethylbicyclo[2.2.2]octo-7-ene-2,3,5,6-tetracarboxylic dianhydride; bicyclo[4.2.0]octane-3,4,7,8-tetracarboxylic dianhydride; bicyclo[4.2.0]Octane-3,4,7,8-tetracarboxylic dianhydride; rel-(1R,1’S,3R,3’S,4S,4’R)-dicyclohexyl-3,3’,4,4’-tetracarboxylic dianhydride; rel-(1R,1’S,3R,3’S,4R,4’S)-dicyclohexyl-3,3’,4,4’-tetracarboxylic dianhydride; dicyclohexyl-1R,1’S,2S,2R’,3R,3S’-tetracarboxylic dianhydride; dicyclohexyl-2,3’,3,4’-tetracarboxylic dianhydride; 5,5’-oxybis(hexahydro-1,3-isobenzofurandione); 5,5’-(1-methylethylidene)bis[hexahydro-1,3-isobenzofurandione]; 5,5’-methylenebis(hexahydro-1,3-isobenzofurandione); 5,5’-carbonylbis(hexahydroisobenzofuran-1,3-dione); 1,2,3,4-cyclopentanetetracarboxylic dianhydride; 1,2-bis(4’-oxa-3’,5-dioxotricyclo-[4.3.0.1. 2,5 decane-8’-yloxy)ethane; 1,3-dimethyl-1,2,3,4-cyclobutane-tetracarboxylic (cyclobutanete-tracarboxylic) dianhydride; 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, norbornane-2-spiro-α-cyclohexanone-α’-spiro-2’’-norbornane-5,5’’,6,6’’-tetracarboxylic dianhydride; cyclopentanonebis-spiro-norbornanetetracarboxylic dianhydride; 1,2,4-cyclopentanetricarboxylic acid-3-(carboxy-methyl)-1,4:2,3-dianhydride; 3,3’-(1,4-piperazinediyl)bis[dihydro-2,5-furandione]; bicyclo[2.2.1]-heptane-2-methanecarboxyl-3,5,6-tricarboxyl-2,3:5,6-dianhydride, 2R,5R,7S,10S-naphthalenetetracarboxylic dianhydride; pentacyclo[8.2.1.1 4’7 0 2’9 0 3’8]Tetradecane-5,6,11,12-tetracarboxylic dianhydride; Tricyclo[4.2.2.02,5]deca-7-ene-3,4,9,10-tetracarboxylic 3,4:9,10-dianhydride; Dodecahydro-1H-4,11:5,9-dimethanofluoreno[2,3-c:6,7-c']difuran-1,3,6,8(3aH)-tetraone; Tetradecahydro-4,10:5,9-dimethanonaphtho[2'',3'':3,4;6'',7'':3',4']dicyclobuta[1,2-c:1',2'-c']difuran-1,3,6,8-tetron,1,2,3,4-butanetetracarboxylic dianhydride; 5,5'-thiobis[hexahydro-4, Examples include 7-methanoisobenzofuran-1,3-dione; 1,1,2,2-ethanetetracarboxylic dianhydride; 5,5'-sulfonylbis(hexahydro-4,7-ethanoisobenzofuran-1,3-dione); 5R,5'R-5,5'-exo-(1,1,3,3,5,5-hexamethyltrisiloxane-1,5-diyl)bisbicyclo[2.2.1]heptane-endo-2,3-dicarboxylic anhydride; 5S,5'S-5,5'-exo-(1,1,3,3,5,5-hexamethyltrisiloxane-1,5-diyl)bisbicyclo[2.2.1]heptane-endo-2,3-dicarboxylic anhydride, etc., and any combination thereof.

[0049] The stoichiometric ratio of diamine 102 to dianhydride 104 added during the mixing step may be approximately 2:1 to approximately 1:2 (or approximately 1.5:1 to approximately 1:1.5, or approximately 1.2:1 to approximately 1:1.2).

[0050] The polycondensation reaction conditions may include a temperature of approximately 40°C or lower (or approximately -20°C to approximately 40°C, or approximately -20°C to approximately 30°C, or approximately -10°C to approximately 25°C) and an ambient pressure of ± approximately 0.1 MPa. Preferably, the polycondensation reaction is completed. This completion may take approximately 4 hours to approximately 48 hours or more (or approximately 4 hours to approximately 24 hours, or approximately 12 hours to approximately 48 hours, or longer).

[0051] While not limited by theory, with respect to the high-boiling point solvent 106, water is considered capable of decomposing the diamine 102. Therefore, the high-boiling point solvent 106 preferably contains about 0.1% by weight or less (or 0% to about 0.1% by weight, or 0% to about 0.01% by weight, or 0% to about 0.001% by weight) of water. To reduce exposure to water during mixing (108) and exposure to polycondensation reaction conditions (110), mixing (108) and exposure (110) may preferably be carried out under a dry atmosphere (e.g., dry nitrogen, dry argon, etc.). Those skilled in the art will recognize that there are multiple apparatus configurations and methods for carrying out these steps in a manner that reduces exposure to water.

[0052] The high-boiling-point solvent 106 has a boiling point higher than the temperature at which the precursor emulsion polymerizes (i.e., the temperature used in the method for polymerizing PAA to form polyimide). In some embodiments, the high-boiling-point solvent 106 has a boiling point at least about 5°C, or about 5°C to about 100°C, or about 10°C to about 70°C higher than the temperature at which the precursor emulsion polymerizes. The high-boiling-point solvent 106 may have a boiling point of about 110°C to about 200°C (or about 110°C to about 160°C, or about 125°C to about 175°C, or about 140°C to about 200°C) at the pressure at which the PAA polymerizes. That is, generally speaking, the methods described herein are preferably carried out at ambient pressure or approximately ambient pressure (e.g., ambient pressure ± about 0.1 MPa). Therefore, solvents having an IUPAC standard boiling point of about 110°C to about 200°C are preferred. However, those skilled in the art will recognize that the boiling point of a fluid is pressure-dependent, and that increasing the pressure raises the boiling point of a solvent. Therefore, if the whole or part of the method is carried out at a pressure exceeding the ambient pressure, the boiling point of the high-boiling point solvent at such pressure increases is preferably about 110°C to about 200°C, which may expand the list of solvents that may be used in the method described herein.

[0053] Examples of high-boiling point solvents 106 include, but are not limited to, N-methyl-2-pyrrolidone (NMP); N,N-dimethylformamide (DMF); N,N-dimethylacetamide (DMAc); N,N-diethylformamide; N,N-diethylacetamide; N-methylpyrrolidone, dimethyl sulfoxide (DMSO); sulfolane, etc.; and any combination thereof.

[0054] In mixing (108), the components can be added in any order. For example, all three components can be mixed (108) simultaneously. In another example, mixing (108) can be carried out by dissolving the diamine 102 in a high-boiling solvent 106 and then adding the dianhydride 104. The addition of the dianhydride 104 can be bolus (i.e., a single addition), stepwise (e.g., 2 to 10 or more additions over a specified time), sequentially (e.g., dropwise over a specified time), or variations thereof. Not limited to theory, dissolving the diamine first and then adding the dianhydride is thought to reduce the protonation of the diamine, which can gel the diamine and have a disruptive effect on the polycondensation reaction.

[0055] Diamine 102 and dianhydride 104 react via polycondensation to form PAA. Therefore, referring again to Figure 1, by exposing diamine 102 and dianhydride 104 to polycondensation reaction conditions (110), a mixture 112 containing PAA and a high-boiling point solvent 106 is obtained. The mixture 112 may comprise about 10% to about 50% by weight (or about 10% to about 25% by weight, or about 15% to about 30% by weight, or about 25% to about 50%) of PAA, about 45% to about 90% by weight (or about 45% to about 65% by weight, or about 55% to about 85% by weight, or about 65% to about 90%) of a high-boiling point solvent 106, and 0% to about 5% by weight (or 0% to about 2% by weight, or 1% to about 3% by weight, or 2% to about 5%) of unreacted reactants (cumulatively diamine 102 and dianhydride 104).

[0056] Next, PAA can be extracted from mixture 112 (see Figure 2), or the mixture can be used in the following sets (as shown in this example).

[0057] As shown in Figure 1, the mixture 112 is emulsified with the matrix fluid 116, which is immiscible with the emulsifying stabilizer 114 and the high-boiling solvent 106 (118), to produce a precursor emulsion 120. Although not limited by theory, the resulting precursor emulsion 120 is an oil-in-oil emulsion having an outer phase (or continuous phase) containing the matrix fluid 116 and an inner phase (or discontinuous phase) containing PAA dispersed in the high-boiling solvent 106, with the emulsifying stabilizer 114 mainly present at the interface between the outer and inner phases. Small amounts of water may be present in either phase of the oil-in-oil emulsion (e.g., 1% by weight or less or 0.1% by weight or less independently in each phase).

[0058] The emulsifying stabilizer 114 may include nanoparticles (e.g., oxide nanoparticles, carbon black, polymer nanoparticles, and combinations thereof), surfactants, and any combination thereof.

[0059] Oxide nanoparticles may be metal oxide nanoparticles, nonmetal oxide nanoparticles, or mixtures thereof. Examples of oxide nanoparticles include, but are not limited to, silica, titania, zirconia, alumina, iron oxide, copper oxide, tin oxide, boron oxide, cerium oxide, thallium oxide, and tungsten oxide, as well as any combination thereof. Mixed metal oxides and / or nonmetal oxides such as aluminosilicates, borosilicates, and aluminoborosilicates are also included in the term metal oxides. Oxide nanoparticles may be hydrophilic or hydrophobic, and may be natural particles or the result of surface treatment of particles. For example, silica nanoparticles having a hydrophobic surface treatment such as dimethylsilyl or trimethylsilyl may be used in the methods and compositions of this disclosure. In addition, silica with a functional surface treatment such as methacrylate functional groups may be used in the methods and compositions of this disclosure. Non-functionalized oxide nanoparticles may also be suitable for use.

[0060] Examples of commercially available silica nanoparticles include AEROSIL® (registered trademark) available from Evonik (e.g., AEROSIL® R812S (hydrophobic modified surface and 260±30m)). 2 Silica nanoparticles with an average diameter of approximately 7 nm and a BET surface area of ​​1 / g, AEROSIL® RX50 (hydrophobic modified surface and 35±10 m 2 Silica nanoparticles with an average diameter of approximately 40 nm and a BET surface area of ​​1 / g, AEROSIL® 380 (hydrophobic modified surface and 380±30m 2 Examples include, but are not limited to, silica nanoparticles having a surface area of ​​ / g, and any combination thereof.

[0061] Carbon black is another type of nanoparticle that may be present as an emulsifying stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those skilled in the art, and any of them may be used herein. Other nanoparticles capable of absorbing infrared radiation may be used similarly.

[0062] Polymer nanoparticles are another type of nanoparticle that may be used as emulsifying stabilizers (e.g., emulsifying stabilizer 114) in the disclosure herein. Suitable polymer nanoparticles may comprise one or more polymers that are thermosetting and / or crosslinked so as not to melt when treated by melt emulsification according to the disclosure herein. High molecular weight thermoplastic polymers having high melting or decomposition points may also constitute suitable polymer nanoparticle emulsifying stabilizers. Examples of polymers suitable for use in polymer nanoparticles include, but are not limited to, polystyrene-co-acrylates, fluorocarbons, silicone-based polymers, and any combination thereof.

[0063] Surfactants can be anionic, cationic, nonionic, or zwitterionic. Examples of surfactants include, but are not limited to, sodium dodecyl sulfate, sorbitan oleate, poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane], sodium doxate (1,4-bis(2-ethylhexoxy)-1,4-dioxabutan-2-sulfonate sodium), fluorocarbon surfactants (e.g., bis(trifluoromethylsulfonyl)amine lithium salt), organosiloxane surfactants, polyoxyalkylene lauryl ethers, polyoxyethylene lauryl ethers, polyoxyethylene oleyl ethers, and polyoxyethylene cetyl ether surfactants, acrylic polymer surfactants, and any combination thereof.Examples of commercially available surfactants include, but are not limited to, CALFAX® DB-45 (sodium dodecyldiphenyl oxide disulfonate available from Pilot Chemicals), SPAN® 80 (sorbitan maleate nonionic surfactant), MERPOL® surfactant (available from Stepan Company), TERGITOL™ TMN-6 (water-soluble, nonionic surfactant, available from DOW), TRITON™ X-100 (octylphenol ethoxylate, available from Sigma-Aldrich), IGEPAL® CA-520 (polyoxyethylene(5) isooctylphenyl ether, available from Sigma-Aldrich), BRIJ® S10 (polyethylene glycol octadecyl ether, available from Sigma-Aldrich), MEGAFAC® surfactant (fluorocarbon surfactant, available from Dainippon Ink), FLUORAD® surfactant (fluorocarbon surfactant, available from 3M), and KP Examples include 341 surfactants (organosiloxane surfactants, available from Shinetsu Chemical Industries), DBE (polyalkylene oxide-modified silicone products, manufactured by Chisso Corporation), POLYFLOW (alkylsiloxane, manufactured by Kyoeisha Chemical Co., Ltd.), GLANOL (silicone compound, manufactured by Kyoeisha Chemical Co., Ltd.), BYK (silicone compound, manufactured by BYK Japan KK), EMULMIN (polyoxyalkylene surfactant, manufactured by Sanyo Chemical Industries, Ltd.), and any combination thereof.

[0064] Surfactants may be present in the mixture at concentrations of approximately 0.01% to 10% by weight (or approximately 0.01% to 1% by weight, or approximately 0.5% to 2% by weight, or approximately 1% to 3% by weight, or approximately 2% to 5% by weight, or approximately 5% to 10% by weight) based on the weight of PAA. Alternatively, the mixture may be surfactant-free (i.e., surfactant-free).

[0065] The weight ratio of nanoparticles to surfactant in the emulsifying stabilizer 114 may be approximately 1:10 to approximately 10:1 (or approximately 1:10 to approximately 1:1, or approximately 1:5 to approximately 5:1, or approximately 1:1 to approximately 10:1).

[0066] The emulsifying stabilizer 114 may be included in the precursor emulsion 120 at a concentration of approximately 0.01% to approximately 10% by weight (or approximately 0.01% to approximately 1% by weight, or approximately 0.1% to approximately 3% by weight, or approximately 1% to approximately 5% by weight, or approximately 5% to approximately 10% by weight) based on the weight of the PAA.

[0067] Examples of matrix fluid 116 include, but are not limited to, degarin, tetralin, silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol (e.g., C1-C4 terminal alkyl groups such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, pearl reem oil, grapeseed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, apricot oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, lanolin esters, oleic acid esters, lauric acid esters, stearic acid esters, aliphatic esters, higher fatty acids, aliphatic alcohols, fatty acid-modified polysiloxanes, aliphatic alcohol-modified polysiloxanes, polyoxyalkylene-modified polysiloxanes, and any combination thereof. Examples of silicone oils include, but are not limited to, polydimethylsiloxane (PDMS), methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and any combination thereof. For example, the matrix fluid 116 may include (a) decalin and / or tetralin, and (b) another of the aforementioned fluids. More specifically, the matrix fluid 116 may contain about 5% to about 40% by weight (or about 5% to about 20% by weight, or about 15% to about 30% by weight, or about 20% to about 40% by weight) of the aforementioned fluids (e.g., silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, or any combination thereof) in decalin and / or tetralin.When decalin and tetralin are used together, their relative weight ratio may be approximately 1:99 to 99:1 (or approximately 1:99 to 50:50, or approximately 25:75 to 75:25, or approximately 50:50 to 99:1).

[0068] The matrix fluid 116 preferably has a boiling point that is (a) greater than the boiling point of the high-boiling solvent 106, and (b) greater than the temperature sufficient to polymerize the PAA. The matrix fluid 116 may be about 150°C to about 450°C or higher (or about 150°C to about 250°C, or about 175°C to about 300°C, or about 250°C to about 450°C, or higher).

[0069] The matrix fluid 116 may be present in the precursor emulsion 120 in an amount of about 40% to about 95% by weight (or about 75% to about 95% by weight, or about 70% to about 90% by weight, or about 55% to about 80% by weight, or about 50% to about 75% by weight, or about 40% to about 60%). The matrix fluid 116 may be present in a weight ratio of matrix fluid 116 to mixture 112 in the range of about 50:50 to about 90:10 (or about 50:50 to about 75:25, or about 60:40 to about 80:20, or about 75:25 to about 90:10).

[0070] Referring again to Figure 1, emulsifying (118) the mixture 112, the emulsifying stabilizer 114, and the matrix fluid 116 may include mixing the components in any order and mixing at a shear rate sufficient to disperse the mixture 112 in the matrix fluid 116. For example, the emulsifying stabilizer 114 may first be dispersed in the matrix fluid 116 before the mixture 112 is added, at a shear rate sufficient to disperse the mixture 112 in the matrix fluid 116. In another example, all three components 112, 114, and 116 may be mixed before the start of shearing. In yet another non-limiting example, the mixture 112 may be mixed with the matrix fluid 116 at a shear rate sufficient to disperse the mixture 112 in the matrix fluid 116. The emulsifying stabilizer 114 can then be added to form the precursor emulsion 120.

[0071] Examples of mixing apparatus used for emulsifying (118) to produce the precursor emulsion 120 include, but are not limited to, extruders (e.g., continuous extruders, batch extruders, etc.), agitated reactors, blenders, reactors equipped with inline homogenizer systems, and apparatus derived therefrom. Here again, water may still be a concern. Those skilled in the art will recognize that there are several mixing apparatus configurations, methods for transferring components, and mixing methods useful for obtaining and processing the precursor emulsion 120 in a manner that reduces exposure to water.

[0072] In the method described herein, the PAA is heated (122) to induce thermal imidization of the PAA. This heating (122) may occur during and / or after emulsification (118). Since the PAA is present in part of the dispersed internal phase of the precursor emulsion 120, heating (122) yields polyimide nanoparticles. Heating (122) the emulsion 120 during and / or after its formation may be done to a temperature sufficient to polymerize the PAA to form polyimide nanoparticles.

[0073] The temperature sufficient for polymerizing PAA may be approximately 100°C to approximately 250°C (or approximately 100°C to approximately 175°C, or approximately 150°C to approximately 200°C, or approximately 175°C to approximately 250°C).

[0074] In method 100, heating (122) the precursor emulsion 120 produces product 124 containing polyimide microparticles, an emulsifying stabilizer 114, and a matrix fluid 116. Depending on the heating temperature, at least a portion of the high-boiling solvent 106 may evaporate during heating (122). Therefore, product 124 may or may not contain the high-boiling solvent 106. Preferably, most of the high-boiling solvent 106 is retained during heating (122). Although not limited to theory, the presence of the high-boiling solvent 106 is thought to promote porosity within the polyimide microparticles.

[0075] Generally, during heating (122), stirring is preferably maintained to keep the inner phase dispersed in the outer phase of the oil-in-oil emulsion. This stirring may be at a speed equal to, less than, or greater than the shear rate sufficient to disperse the mixture 112 in the matrix fluid 116.

[0076] The precursor emulsion 120 can be maintained at a temperature sufficient to polymerize the PAA for a sufficient amount of time to completely polymerize the PAA, which may take about 2 hours to about 24 hours or more (or about 2 hours to about 8 hours, or about 6 hours to about 24 hours, or longer).

[0077] Polyimide particles are generally insoluble in the matrix fluid 116 or the high-boiling solvent 106. Therefore, separation of polyimide particles from the matrix fluid 116 and the high-boiling solvent 106 can be achieved by filtration and washing (with methanol, ethanol, acetone, etc.). After separation, the polyimide particles can be dried.

[0078] Although not limited to theory, the PAA is dispersed in a high-boiling point solvent 106 and then polymerized in situ in the inner phase of the precursor emulsion 120. This is thought to be similar to sol-gel polymerization, which produces a porous morphology rather than solid particles. The morphology is shown in scanning electron microscope (SEM) images in the Examples section below.

[0079] The morphology involves the polyimide forming a porous, irregular skeleton similar to those found in sol-gels and / or aerogels. This is in contrast to the more regular skeletons found in open-cell, closed-cell, and topologically ordered porous structures. The porous, irregular skeleton morphology may include interconnected flake-like and / or ribbon-like structures (e.g., Figure 7D in the Examples) and / or interconnected solidified polymer molten structures (e.g., Figures 9C and 10B in the Examples).

[0080] The emulsifying stabilizer 114 may coat a portion of the surface (outer and / or inner surface) of the polyimide microparticles. The coating may include (a) the emulsifying stabilizer 114 dispersed on the surface (outer and / or inner surface) of the polyimide microparticles, and / or (b) the emulsifying stabilizer 114 embedded on the surface (outer and / or inner surface) of the polyimide microparticles.

[0081] The emulsifying stabilizer 114 can form a coating that covers at least 5% (or about 5% to about 100%, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%) of the outer surface of the polyimide microparticles, where the outer surface refers to the surface of the polyimide microparticles within 1 volume percent of the outer circumference. The coverage rate of the emulsifying stabilizer 114 on the outer surface of the polyimide microparticles can be determined using image analysis with a scanning electron microscope.

[0082] Furthermore, the emulsifying stabilizer 114 can aggregate during the production method 100 and be trapped within the porous, irregular framework of the polyimide microparticles. Figure 10C shows such trapped aggregates of the emulsifying stabilizer 114.

[0083] Figure 1 is a non-limiting exemplary method 100 that exemplifies the present disclosure for producing polyimide particles. Figure 2 is a non-limiting exemplary method 200 that exemplifies another example of the present disclosure for producing polyimide particles. The reference numerals in Figure 2 are used repeatedly, and the disclosures in Figure 1 apply to method 200 in Figure 2.

[0084] Method 200, shown in Figure 2, can produce a mixture 112 containing PAA and a high-boiling solvent 106 using the same steps, conditions, and components disclosed in relation to Figure 1. The difference between Method 200 and Method 100 is that PAA 232 can be separated from the mixture 230 (230), thereby reducing contamination by any unreacted diamine 102 and unreacted dianhydride 104. Separation (230) can be achieved by adding a PAA non-solvent (i.e., a fluid in which PAA is not soluble) to the mixture 112, thereby precipitating PAA 232 from the mixture 112. Examples of PAA non-solvents include, but are not limited to, water, acetone, methanol, and any combination thereof. When water is used, it should be noted that vigorous drying is preferred so that water is present in minimal amounts or not at all in the precursor emulsion 120. Furthermore, when water is used, the temperature of PAA 232 is preferably not above 50°C to mitigate any undesirable reactions. Therefore, when water is used as the non-solvent for PAA, drying the PAA is preferably carried out under reduced pressure at room temperature (e.g., 25°C) (e.g., in a vacuum oven or suitable outdoor apparatus at room temperature).

[0085] After separation (230), PAA232 preferably contains 95% by weight or more of PAA. That is, contaminants such as unreacted diamine 102, unreacted dianhydride 104, any remaining high-boiling point solvent 106, and any PAA non-solvents are 5% by weight or less (or 0% to 5% by weight, or 0.1% to 3% by weight, or 0% to 1% by weight).

[0086] Next, PAA232 may dissolve in a second high-boiling solvent 234 (236) to produce a PAA solution 232. Examples of the second high-boiling solvent 234 include, but are not limited to, DMF; DMAc; N,N-diethyl-formamide; N,N-diethylacetamide; N-methylpyrrolidone (DMSO); sulfolane; and any combination thereof.

[0087] The PAA solution 232 may comprise about 10% to about 50% by weight (about 10% to about 25% by weight, or about 15% to about 30% by weight, or about 25% to about 50%) of PAA 232 and about 50% to about 90% by weight (or about 75% to about 90% by weight, or about 70% to about 85% by weight, or about 50% to about 75%) of a second high-boiling point solvent 234.

[0088] In the illustrated method 200, the PAA solution 232 is used as mixture 112 in the method of Figure 1. That is, as shown in Figure 2, the PAA solution 232 is emulsified (118) with an emulsifying stabilizer 114 and a matrix fluid 116 that is immiscible with the second high-boiling solvent 234 to produce a precursor emulsion 120. Although not limited by theory, the resulting precursor emulsion 120 is an oil-in-oil emulsion having an outer phase containing the matrix fluid 116 and an inner phase containing PAA 232 dispersed in the second high-boiling solvent 234, with the emulsifying stabilizer 114 mainly present at the interface between the outer and inner phases. Thus, the disclosure of mixture 112 related to emulsification (118) in Figure 1 applies to the PAA solution 232 in Figure 2. For example, the PAA solution 232 may exist in a weight ratio of matrix fluid 116 to PAA solution 232 in the range of approximately 50:50 to approximately 90:10 (or approximately 50:50 to approximately 75:25, or approximately 60:40 to approximately 80:20, or approximately 75:25 to approximately 90:10). Furthermore, the order in which components 238, 114, and 116 are mixed is the same as the order described for components 112, 114, and 116 in Figure 1.

[0089] Method 200, shown in the figure, comprises the steps, composition, and method parameters of the method described in Figure 1 for obtaining product 124, as well as any other further steps described, including but not limited to filtration, washing, and drying. In addition, the believed theory of how PAA polymerizes to form polyimide particles having a porous, irregular skeletal morphology is applied to Method 200 in Figure 2.

[0090] The polyimide microparticles of this disclosure (for example, prepared by Method 100 in Figure 1, Method 200 in Figure 2, or a modified version of either method) may contain about 90% by weight or more (or about 90% to about 100% by weight, or about 95% to about 100% by weight, or about 98% to about 100% by weight, or about 99% to about 100%) of polyimide, with the remainder being an emulsifying stabilizer and unpolymerized PAA. Preferably, the amount of unpolymerized PAA is 1% by weight or less (or 0% to about 1% by weight, or 0% to about 0.1% by weight). The polyimide microparticles of this disclosure may consist of polyimide, an emulsifying stabilizer, and unpolymerized PAA. The polyimide microparticles of this disclosure may consist of polyimide and an emulsifying stabilizer. The polyimide microparticles of this disclosure may consist of polyimide.

[0091] The polyimide particles of this disclosure may have an average diameter (D50 based on volume) of about 10 μm to about 200 μm (or about 10 μm to about 50 μm, or about 25 μm to about 100 μm, or about 75 μm to about 150 μm, or about 125 μm to about 200 μm).

[0092] The polyimide microparticles of this disclosure may have D10 of about 0.5 μm to about 50 μm (or about 0.5 μm to about 25 μm, or about 5 μm to about 30 μm, or about 10 μm to about 50 μm), D50 of about 10 μm to about 200 μm (or about 10 μm to about 50 μm, or about 25 μm to about 100 μm, or about 75 μm to about 150 μm, or about 125 μm to about 200 μm), and D90 of about 50 μm to about 300 μm (or about 50 μm to about 150 μm, or about 75 μm to about 200 μm, or about 100 μm to about 300 μm), and D10 <D50<D90である。

[0093] The polyimide microparticles of this disclosure may also have a particle size span of about 0.2 to about 10 (or about 0.2 to about 2, or about 0.4 to about 1, or about 0.5 to about 1, or about 1 to about 3, or about 2 to about 5, or about 5 to about 10). A diameter span value of 1.0 or greater is considered broad, and a diameter span value of 0.75 or less is considered narrow.

[0094] The polyimide microparticles of this disclosure may have a roundness of about 0.9 or more (or about 0.90 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to 1.0).

[0095] The polyimide microparticles of this disclosure may have an angle of repose of about 25° to about 45° (or about 25° to about 35°, or about 30° to about 40°, or about 35° to about 45°).

[0096] The polyimide microparticles of this disclosure may have a Hausner ratio of about 1.0 to about 1.5 (or about 1.0 to about 1.2, or about 1.1 to about 1.3, or about 1.2 to about 1.35, or about 1.3 to about 1.5).

[0097] The polyimide microparticles disclosed herein have a density of approximately 0.2 g / cm³. 3 ~about 0.8g / cm 3 (or approximately 0.2 g / cm³) 3 ~Approximately 0.4g / cm³ 3 , or approximately 0.3 g / cm³ 3 ~about 0.6g / cm 3 , or approximately 0.4 g / cm³ 3 ~about 0.7g / cm 3 , or approximately 0.5 g / cm³ 3 ~about 0.6g / cm 3 , or approximately 0.5 g / cm³ 3 ~about 0.8g / cm 3 It may have a bulk density of ).

[0098] The polyimide microparticles of this disclosure are approximately 30m 2 / g~about 500m 2 / g (or approximately 30m 2 / g~about 150m 2 / g, or approximately 100m 2 / g ~ approx. 250m 2 / g, or approximately 200m 2 / g ~ approx. 350m 2 / g, or 300m 2 / g~about 500m 2 It may have a BET surface area of ​​( / g).

[0099] The polyimide nanoparticles of this disclosure may have a sintering window of about 15°C to about 35°C (or about 15°C to about 25°C, or about 25°C to about 35°C).

[0100] The polyimide fine particles of this disclosure may have a melting point of about 250°C to about 400°C (or about 250°C to about 350°C, or about 300°C to about 400°C).

[0101] The polyimide nanoparticles of this disclosure may have a glass transition temperature of about 200°C to about 350°C (or about 200°C to about 300°C, or about 250°C to about 350°C).

[0102] The polyimide fine particles of this disclosure may have a decomposition temperature of about 400°C to about 500°C (or about 400°C to about 475°C, or about 450°C to about 500°C).

[0103] The polyimide fine particles of this disclosure may have a crystallization temperature of about 250°C to about 300°C (or about 250°C to about 275°C, or about 275°C to about 300°C).

[0104] The polyimide microparticles of this disclosure may have a degree of crystallinity of about 20% to about 60% (or about 20% to about 40%, or about 30% to about 50%, or about 40% to about 60%).

[0105] The polyimide microparticles of this disclosure may have an MFI flow rate of about 0.5 g / 10 min to about 10 g / 10 min (or about 0.5 g / 10 min to about 2 g / 10 min, or about 1 g / 10 min to about 5 g / 10 min, or about 3 g / 10 min to about 10 g / 10 min).

[0106] Purpose

[0107] The polyimide microparticles of this disclosure can be used to manufacture various articles by SLS additive manufacturing. As a non-limiting example, the SLS additive manufacturing method of this disclosure includes optionally depositing the polyimide microparticles of this disclosure together with thermoplastic polymer particles (preferably of similar size and shape, but which may be porous or solid) on a surface (e.g., in layers and / or in a specific shape), and, upon deposition, heating at least a portion of the polyimide microparticles to promote solidification and form a solidified body (or object). The solidified body may have a porosity (percentage of volume that is void) of about 20% or less (e.g., 5% to about 20%, or about 5% to about 15%, or about 10% to about 20%). For example, heating and solidification of the polyimide microparticles, and optionally the thermoplastic polymer particles, may be carried out in a laser-based 3D printing apparatus such that heating and solidification are performed by selective laser sintering.

[0108] Examples of thermoplastic polymers that may contain all or part of thermoplastic polymer particles include, but are not limited to, polyamides, polyurethanes, polyethylene (preferably functionalized polyethylene), polypropylene (preferably functionalized polypropylene), polyacetals (which may be in the presence of polyethylene glycol), polycarbonates (e.g., maleized polyalkenes (maleized PP or EPR), polyesteramides, acrylonitrile butadiene styrene (ABS), and maleized ABS (MA-g-ABS), butadiene-styrene-acrylonitrile-acrylate Copolymers, styrene-maleic anhydride (SMA), styrene-propylene-ethylene-butylene-styrene (SEBS) and MA-g-SEBS, polyethyl oxazoline, ethylene-glycidyl methacrylate graft copolymer (may be in the presence of compatibilizers), polybutyl terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), ethylene vinyl acetate copolymer (EVA), ethylene polypylene diene rubber (EPDM), ethylene elastomer (ethylenecelastomer)(EPR) (may be in the presence of a compatibilizer such as MA-grafted ethylene propylene copolymer, for example), poly(4-methyl-1-pentene), polyhexamethylene terephthalate, polystyrene (e.g., statistical or block styrene copolymer, grafted styrene, or compatibilizer), polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone (PESU), polysulfone (PSU) (preferably functionalized PSU), polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamide-imide, polyetherimide, polyetherether, copolymer containing polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or Examples include ungrafted thermoplastic polyamides, functionalized or unfunctionalized ethylene / vinyl monomer polymers, functionalized or unfunctionalized ethylene / alkyl (meth)acrylates, functionalized or unfunctionalized (meth)acrylic acid polymers, functionalized or unfunctionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorided or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF) (which may be in compatibilization with polyetheramide block copolymers), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrene block copolymers, polyacrylonitrile, silicones, and any combination thereof. Copolymers containing one or more of the above may also be used in the methods and systems of this disclosure.

[0109] Examples of articles that can be manufactured by a method that uses polyimide microparticles (optionally in combination with thermoplastic polymer particles) to form all or part of an article include, but are not limited to, particles, films, packaging materials, toys, household goods, automotive parts, aerospace / aircraft parts, containers (e.g., containers for food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, furniture parts, decorative household goods, plastic gears, screws, nuts, bolts, cable ties, jewelry, works of art, statues, medical items, prosthetics, orthopedic implants, manufacturing artifacts to aid learning in education, 3D anatomical models to assist surgery, robotics products, biomedical devices (orthotics), household appliances, dental products, electronic equipment, sporting goods, functional elements of high-temperature fuel cells, chemical and environmental applications, military applications, solar cells, and flexible printed circuits. Furthermore, the particles may be useful in applications such as paints, powder coatings, inkjet materials, electrophotographic toners, and 3D printing, but are not limited to these.

[0110] In addition, the morphology of polyimide microparticles increases the surface area of ​​the microparticles compared to solid microparticles of the same dimensions, and polyimide provides high-temperature stability. Therefore, the polyimide microparticles described herein are suitable for use as catalyst carriers in applications such as the fabrication of high-surface-area films, gas storage, carbon recovery, contaminant removal, molecular separation, catalysis, drug delivery, sensing, and polymer molecular sieve films. Exemplary Embodiments

[0111] The first non-limiting exemplary embodiment includes mixing a diamine and a dianhydride in a first dry high-boiling solvent, reacting the diamine and the dianhydride to produce a mixture comprising poly(amic acid) (PAA) and the first dry high-boiling solvent, using an emulsifying stabilizer to emulsify the mixture in a matrix fluid immiscible with the first dry high-boiling solvent to form a precursor emulsion that is an oil-in-oil type emulsion, and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide microparticles during and / or after formation.

[0112] The first non-limiting exemplary embodiment may further include one or more of the following: Element 1: The diamine is selected from the diamines described herein; Element 2: The dianhydride is selected from the dianhydrides described herein; Element 3: The reaction between the diamine and the dianhydride is at about 40 °C or lower; Element 4: The reaction between the diamine and the dianhydride spans from about 6 hours to about 48 hours; Element 5: The stoichiometric ratio of diamine to dianhydride is from about 2:1 to about 1:2; Element 6: Performing the reaction between the diamine and the dianhydride includes dissolving the diamine in the first dry high-boiling solvent and adding the dianhydride to the first dry high-boiling solvent in which the diamine is dissolved; Element 7: The emulsifying stabilizer includes a surfactant and / or nanoparticles; Element 8: The emulsifying stabilizer is present as a coating on the surface of the polyimide particles; Element 9: The temperature sufficient to polymerize the PAA is from about 100 °C to about 250 °C; Element 10: The method further includes washing the polyimide microparticles and drying the polyimide microparticles after washing; Element 11: The polyimide microparticles have a D10 of about 0.5 μm to about 50 μm, a D50 of about 10 μm to about 200 μm, and a D90 of about 50 μm to about 300 μm, with D10 < D50 < D90; Element 12: The polyimide microparticles have a particle size span of about 0.2 to about 10; Element 13: The polyimide microparticles have a circularity of about 0.9 or greater (or about 0.90 to about 1.0); Element 14: The polyimide microparticles have an angle of repose of about 25° to about 45°; Element 15: The polyimide microparticles have a Hausner ratio of about 1.0 to about 1.5; Element 16: The polyimide microparticles have a density of about 0.2 g / cm 3~about 0.8g / cm 3 It has a bulk density of ; Element 17: Polyimide fine particles are approximately 30 m 2 / g~about 500m 2Element 18: Polyimide microparticles have a BET surface area of ​​15°C to 35°C; Element 19: Polyimide microparticles have a melting point of 250°C to 400°C; Element 20: Polyimide microparticles have a glass transition temperature of 200°C to 350°C; Element 21: Polyimide microparticles have a decomposition temperature of 400°C to 500°C; Element 22: Polyimide microparticles have a crystallization temperature of 250°C to 300°C; Element 23: Polyimide microparticles have a degree of crystallinity of 20% to 60%; Element 24: Polyimide microparticles have an MFI flow rate of 0.5 g / 10 min to 10 g / 10 min; and Element 25: Polyimide microparticles have a porous, irregular skeletal structure including (a) a flake-like structure, (b) a ribbon-like structure, (c) and / or an interconnected solidified polymer molten structure.Examples of combinations, though not limited to them, include: Element 1 combined with one or more elements from 2 to 25; Element 2 combined with one or more elements from 3 to 25; Element 3 combined with one or more elements from 4 to 25; Element 4 combined with one or more elements from 5 to 25; Element 5 combined with one or more elements from 6 to 25; Element 6 combined with one or more elements from 7 to 25; Element 7 combined with one or more elements from 8 to 25; Element 8 combined with one or more elements from 9 to 25; Element 1 combined with one or more elements from 9 to 25; Element 1 combined with one or more elements from 10 to 25; Element 10 combined with one or more elements from 11 to 25; Element 11 combined with elements from 12 to 25 Examples include combinations of one or more of the following: element 12 combined with one or more of elements 13-25; element 13 combined with one or more of elements 14-25; element 14 combined with one or more of elements 15-25; element 15 combined with one or more of elements 16-25; element 16 combined with one or more of elements 17-25; element 17 combined with one or more of elements 18-25; element 18 combined with one or more of elements 19-25; element 19 combined with one or more of elements 20-25; element 20 combined with one or more of elements 21-25; element 21 combined with one or more of elements 22-25; and combinations of two or more of elements 22-25.

[0113] A second non-limiting exemplary embodiment is a composition comprising polyimide fine particles produced by the method of the first non-limiting exemplary embodiment.

[0114] A third non-limiting exemplary embodiment is a method comprising optionally depositing polyimide fine particles of the second non-limiting exemplary embodiment onto a surface (for example, in layers and / or in a specific shape) in combination with thermoplastic polymer particles (preferably of similar size and shape, but which may be porous or solid), and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object).

[0115] A fourth non-limiting exemplary embodiment is a method comprising: mixing a diamine and a dianhydride in a first dry high-boiling solvent; reacting the diamine and the dianhydride to produce a mixture containing poly(amidic acid) (PAA) and the first dry high-boiling solvent; extracting the PAA from the mixture; dissolving the PAA in a second dry high-boiling solvent to produce a PAA solution; emulsifying the PAA solution in a matrix fluid immiscible with the first dry high-boiling solvent using an emulsifying stabilizer to form a precursor emulsion which is an oil-in-oil emulsion; and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide fine particles during and / or after formation. A fourth non-limiting exemplary embodiment may further include one or more of the elements 1; 2; 3; 4; 5; 6; 7; 8; 9; 10; 11; 12; 13; 14; 15; 16; 17; 18; 19; 20; 21; 22; 23; 24; and 25 (including any combination thereof).

[0116] A fifth non-limiting exemplary embodiment is a composition comprising polyimide fine particles produced by the method of the fourth non-limiting exemplary embodiment.

[0117] A sixth non-limiting exemplary embodiment is a method comprising optionally depositing polyimide fine particles of the fifth non-limiting exemplary embodiment onto a surface (for example, in layers and / or in a specific shape) in combination with thermoplastic polymer particles (preferably of similar size and shape, but which may be porous or solid), and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object).

[0118] A seventh non-limiting exemplary embodiment is a composition comprising polyimide fine particles, wherein the fine particles have a porous, irregular skeletal structure comprising (a) a flake-like structure, (b) a ribbon-like structure, (c) and / or an interconnected solidified polymer molten structure. A fifth non-limiting exemplary embodiment may further comprise one or more of elements 11; 12; 13; 14; 15; 16; 17; 18; 19; 20; 21; 22; 23; and 24 (including combinations thereof).

[0119] An eighth non-limiting exemplary embodiment is a method comprising optionally depositing polyimide fine particles of the seventh non-limiting exemplary embodiment onto a surface (for example, in layers and / or in a specific shape) in combination with thermoplastic polymer particles (preferably of similar size and shape, but which may be porous or solid), and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object). Clause

[0120] Clause 1: A method comprising: mixing a diamine and a dianhydride in a first dry high-boiling point solvent; reacting the diamine and the dianhydride to produce a mixture comprising poly(amidic acid) (PAA) and the first dry high-boiling point solvent; emulsifying the mixture in a matrix fluid immiscible with the first dry high-boiling point solvent using an emulsifying stabilizer to form a precursor emulsion which is an oil-in-oil emulsion; and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide fine particles during and / or after its formation.

[0121] Clause 2: The method described in Clause 1, wherein the diamine is selected from the diamines described herein.

[0122] Clause 3: The method described in Clause 1, wherein the dianhydrous is selected from the dianhydrous described herein.

[0123] Clause 4: The method according to Clause 1, wherein the reaction between the diamine and the dianhydride is carried out at a temperature of approximately 40°C or below.

[0124] Clause 5: The reaction of the diamine with the dianhydride is carried out according to the method in Clause 1, for a period of approximately 6 to 48 hours.

[0125] Clause 6: The method according to Clause 1, wherein the stoichiometric ratio of the diamine to the dianhydride is approximately 2:1 to approximately 1:2.

[0126] Clause 7: The method according to Clause 1, wherein carrying out the reaction of a diamine with a dianhydride comprises dissolving the diamine in a first dry high-boiling point solvent and adding the dianhydride to the first dry high-boiling point solvent in which the diamine is dissolved.

[0127] Clause 8: The method according to Clause 1, wherein the emulsifying stabilizer comprises a surfactant and / or nanoparticles.

[0128] Clause 9: The emulsifying stabilizer is present as a coating on the surface of the polyimide particles, as described in Clause 1.

[0129] Clause 10: The method according to Clause 1, wherein the temperature sufficient to polymerize PAA is from about 100°C to about 250°C.

[0130] Clause 11: The method according to Clause 1, further comprising washing the polyimide microparticles and drying the polyimide microparticles after washing.

[0131] Clause 12: The method according to Clause 1, wherein the polyimide microparticles have a D10 of from about 0.5 μm to about 50 μm, a D50 of from about 10 μm to about 200 μm, and a D90 of from about 50 μm to about 300 μm, with D10 < D50 < D90.

[0132] Clause 13: The method according to Clause 1, wherein the polyimide microparticles have a particle size span of from about 0.2 to about 10.

[0133] Clause 14: The method according to Clause 1, wherein the polyimide microparticles have a circularity of about 0.9 or more (or from about 0.90 to about 1.0).

[0134] Clause 15: The method according to Clause 1, wherein the polyimide microparticles have an angle of repose of from about 25° to about 45°.

[0135] Clause 16: The method according to Clause 1, wherein the polyimide microparticles have a Hausner ratio of from about 1.0 to about 1.5.

[0136] Clause 17: The method according to Clause 1, wherein the polyimide microparticles have a bulk density of from about 0.2 g / cm 3 to about 0.8 g / cm 3 Clause 18: The method according to Clause 1, wherein the polyimide microparticles have a BET surface area of from about 30 m

[0137] / g to about 500 m 2 / g. 2 Clause 19: The method according to Clause 1, wherein the polyimide microparticles have a sintering window of from about 15°C to about 35°C.

[0138] Clause 19: The method according to Clause 1, wherein the polyimide microparticles have a sintering window of from about 15°C to about 35°C.

[0139] Clause 20: The polyimide fine particles have a melting point of about 250°C to about 400°C, as described in Clause 1.

[0140] Clause 21: The method according to Clause 1, wherein the polyimide microparticles have a glass transition temperature of approximately 200°C to approximately 350°C.

[0141] Clause 22: The polyimide fine particles have a decomposition temperature of approximately 400°C to approximately 500°C, as described in Clause 1.

[0142] Clause 23: The polyimide fine particles have a crystallization temperature of approximately 250°C to approximately 300°C, as described in Clause 1.

[0143] Clause 24: The polyimide microparticles have a degree of crystallinity of about 20% to about 60% as described in Clause 1.

[0144] Clause 25: The method according to Clause 1, wherein the polyimide microparticles have an MFI flow rate of about 0.5 g / 10 min to about 10 g / 10 min.

[0145] Clause 26: The method according to Clause 1, wherein the polyimide microparticles have a porous, irregular skeletal structure comprising (a) a flake-like structure, (b) a ribbon-like structure, (c) and / or an interconnected solidified polymer molten structure.

[0146] Clause 27: A composition comprising polyimide fine particles as described in Clause 1.

[0147] Clause 28: A method comprising optionally depositing polyimide fine particles described in Clause 27 onto a surface together with thermoplastic polymer particles, and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object).

[0148] Clause 29: A method comprising: mixing a diamine and a dianhydride in a first dry high-boiling solvent; reacting the diamine and the dianhydride to produce a mixture containing poly(amidic acid) (PAA) and the first dry high-boiling solvent; extracting the PAA from the mixture; dissolving the PAA in a second dry high-boiling solvent to produce a PAA solution; emulsifying the PAA solution in a matrix fluid immiscible with the first dry high-boiling solvent using an emulsifying stabilizer to form a precursor emulsion which is an oil-in-oil emulsion; and heating the precursor emulsion to a temperature sufficient to polymerize the PAA to form polyimide fine particles during and / or after its formation.

[0149] Clause 30: The method described in Clause 29, wherein the diamine is selected from the diamines described herein.

[0150] Clause 31: Dianhydrous is selected from the dianhydrous described herein, as described in Clause 29.

[0151] Clause 32: The method according to Clause 29, wherein the reaction of the diamine with the dianhydride is carried out at a temperature of about 40°C or below.

[0152] Clause 33: The reaction of the diamine with the dianhydride is carried out according to the method described in Clause 29, for a period of approximately 6 to 48 hours.

[0153] Clause 34: The stoichiometric ratio of diamine to dianhydride is approximately 2:1 to approximately 1:2, as described in Clause 29.

[0154] Clause 35: The method according to Clause 29, wherein carrying out the reaction of a diamine with a dianhydride comprises dissolving the diamine in a first dry high-boiling point solvent and adding the dianhydride to the first dry high-boiling point solvent in which the diamine is dissolved.

[0155] Clause 36: The method according to Clause 29, wherein the emulsifying stabilizer comprises a surfactant and / or nanoparticles.

[0156] Clause 37: The emulsifying stabilizer is the method described in Clause 29 that exists as a coating on the surface of the polyimide particles.

[0157] Clause 38: The temperature sufficient to polymerize PAA is from about 100 °C to about 250 °C, the method described in Clause 29.

[0158] Clause 39: The method further includes washing the polyimide microparticles and drying the polyimide microparticles after washing, the method described in Clause 29.

[0159] Clause 40: The polyimide microparticles have a D10 of about 0.5 μm to about 50 μm, a D50 of about 10 μm to about 200 μm, and a D90 of about 50 μm to about 300 μm, and D10 < D50 < D90, the method described in Clause 29.

[0160] Clause 41: The polyimide microparticles have a particle size span of about 0.2 to about 10, the method described in Clause 29.

[0161] Clause 42: The polyimide microparticles have a circularity of about 0.9 or more (or about 0.90 to about 1.0), the method described in Clause 29.

[0162] Clause 43: The polyimide microparticles have an angle of repose of about 25° to about 45°, the method described in Clause 29.

[0163] Clause 44: The polyimide microparticles have a Hausner ratio of about 1.0 to about 1.5, the method described in Clause 29. <00##

[0164] Clause 45: The polyimide microparticles have a bulk density of about 0.2 g / cm 3 ~ about 0.8 g / cm 3 and the method described in Clause 29.

[0165] Clause 46: The polyimide microparticles have a BET surface area of about 30 m 2 / g to about 500 m 2 / g, the method described in Clause 29.

[0166] Clause 47: The method according to Clause 29, wherein the polyimide fine particles have a sintering window of about 15°C to about 35°C.

[0167] Clause 48: Polyimide fine particles having a melting point of about 250°C to about 400°C, as described in Clause 29.

[0168] Clause 49: The method according to Clause 29, wherein the polyimide nanoparticles have a glass transition temperature of about 200°C to about 350°C.

[0169] Clause 50: The polyimide fine particles have a decomposition temperature of approximately 400°C to approximately 500°C, as described in Clause 29.

[0170] Clause 51: The polyimide fine particles have a crystallization temperature of approximately 250°C to approximately 300°C, as described in Clause 29.

[0171] Clause 52: The polyimide microparticles having a degree of crystallinity of about 20% to about 60% as described in Clause 29.

[0172] Clause 53: Polyimide microparticles as described in Clause 29, having an MFI flow rate of about 0.5 g / 10 min to about 10 g / 10 min.

[0173] Clause 54: The method according to Clause 29, wherein the polyimide microparticles have a porous, irregular skeletal structure comprising (a) a flake-like structure, (b) a ribbon-like structure, (c) and / or an interconnected solidified polymer molten structure.

[0174] Clause 55: A composition comprising polyimide fine particles as described in Clause 29.

[0175] Clause 56: A method comprising optionally depositing polyimide fine particles described in Clause 55 together with thermoplastic polymer particles on a surface, and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object).

[0176] Clause 57: A composition comprising fine particles containing polyimide, wherein the fine particles have a porous irregular skeletal morphology including (a) a flake-like structure, (b) a ribbon-like structure, (c), and / or an interconnected solidified polymer melt structure.

[0177] Clause 58: The composition according to Clause 57, wherein the polyimide fine particles have a D10 of about 0.5 μm to about 50 μm, a D50 of about 10 μm to about 200 μm, and a D90 of about 50 μm to about 300 μm, and D10 < D50 < D90.

[0178] Clause 59: The composition according to Clause 57, wherein the polyimide fine particles have a particle size span of about 0.2 to about 10.

[0179] Clause 60: The composition according to Clause 57, wherein the polyimide fine particles have a circularity of about 0.9 or more (or about 0.90 to about 1.0).

[0180] Clause 61: The composition according to Clause 57, wherein the polyimide fine particles have an angle of repose of about 25° to about 45°.

[0181] Clause 62: The composition according to Clause 57, wherein the polyimide fine particles have a Hausner ratio of about 1.0 to about 1.5.

[0182] Clause 63: The polyimide fine particles have a bulk density of about 0.2 g / cm 3 ~about 0.8 g / cm 3 The composition according to Clause 57.

[0183] Clause 64: The composition according to Clause 57, wherein the polyimide fine particles have a BET surface area of about 30 m 2 / g to about 500 m 2 / g.

[0184] Clause 65: The composition according to Clause 57, wherein the polyimide fine particles have a sintering window of about 15°C to about 35°C.

[0185] Clause 66: The composition according to Clause 57, wherein the polyimide fine particles have a melting point of about 250°C to about 400°C.

[0186] Clause 67: The composition according to Clause 57, wherein the polyimide microparticles have a glass transition temperature of about 200°C to about 350°C.

[0187] Clause 68: The composition according to Clause 57, wherein the polyimide fine particles have a decomposition temperature of about 400°C to about 500°C.

[0188] Clause 69: The composition according to Clause 57, wherein the polyimide fine particles have a crystallization temperature of about 250°C to about 300°C.

[0189] Clause 70: The composition according to Clause 57, wherein the polyimide microparticles have a degree of crystallinity of about 20% to about 60%.

[0190] Clause 71: The composition according to Clause 57, wherein the polyimide microparticles have an MFI flow rate of about 0.5 g / 10 min to about 10 g / 10 min.

[0191] Clause 72: The composition according to Clause 57, wherein the polyimide microparticles have a porous, irregular skeletal structure comprising (a) a flake-like structure, (b) a ribbon-like structure, (c) and / or an interconnected solidified polymer molten structure.

[0192] Clause 73: A composition comprising polyimide fine particles as described in Clause 29.

[0193] Clause 74: A method comprising optionally depositing polyimide fine particles described in Clause 57 onto a surface together with thermoplastic polymer particles, and, upon deposition, heating at least a portion of the polyimide fine particles to promote their solidification and form a solidified body (or object).

[0194] Unless otherwise stated, all numbers used herein and in the related claims, representing quantities of components, properties such as molecular weight, and reaction conditions, should in all cases be understood as being modified by the term “approximately.” Therefore, unless otherwise indicated, the numerical parameters described in the following specification and the appended claims are approximations that may vary depending on the desired properties expected to be obtained by the embodiment of the present invention. At the very least, without any intention to limit the application of the doctrine of equivalents to the claims, each numerical parameter should be interpreted by applying the usual rounding method in light of the number of significant figures reported.

[0195] One or more exemplary embodiments incorporating one or more inventive elements are presented herein. For clarity, not all features of physical implementations are described or represented in this application. It is understood that in developing physical embodiments incorporating one or more elements of the present invention, numerous implementation-specific decisions must be made to achieve the developer's goals, such as implementation and compliance with system-related, business-related, government-related, and other constraints that change over time. While the developer's efforts may be time-consuming, such efforts are nevertheless routine for those skilled in the art and will benefit from this disclosure.

[0196] Although compositions and methods are described herein using the term “containing” various components or processes, compositions and methods may also “essentially consist of” or “consist of” various components and processes.

[0197] To facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are provided. The following examples should not be interpreted in any way as limiting or defining the scope of the present invention. [Examples]

[0198] Example 1 - Polycondensation Step: A 250 mL three-necked round-bottom flask equipped with a magnetic stirrer and nitrogen inlet / outlet was filled with 1,12-diaminododecane (9.11 g, 98%, SigmaAldrich), and anhydrous 1-methyl-2-pyrrolidinone (100 g, 99.5%, SigmaAldrich) was added using a cannula. The mixture was stirred at 300 rpm at 80°C for 1 hour and then cooled to room temperature under an inert nitrogen atmosphere. Pyromelitic dianhydride (9.990 g, 97%, SigmaAldrich) was then added in five portions at 1-hour intervals. After the addition of pyromelitic dianhydride was complete, the reaction was allowed to continue at room temperature for 24 hours to complete polymerization and the formation of PAA as a yellowish viscose liquid. The resulting PAA was precipitated by adding 200 mL of deionized water to the reactor. The resulting colloidal mixture was filtered using a Buchner funnel and washed once each with methanol, formic acid, and acetone. The resulting wet cake was dried under vacuum for two days to obtain a white PAA powder in quantitative yield.

[0199] Using infrared spectroscopy, 1560 cm -1 and 1698cm -1 The peak at 2400cm -1 ~3300cm -1 A broad peak at 1703 cm (evidence of the presence of a deprotonated carboxylic acid functional group), and at 1703 cm. -1 Based on the presence of a peak (evidence of the presence of an amide functional group) in the sample, the presence of PAA was confirmed.

[0200] Example 2 - Emulsion Sol-Gelimidization Step: A 250 mL three-necked glass cylindrical reaction vessel equipped with an overhead stirrer, a P4 impeller, nitrogen inlet / outlet, and an electronic thermometer was filled with a DMF solution of PAA (2.30 g total, 20% PAA in DMF), a decalin solution of PDMS (10 kcSt PDMS, 11.5 g total, 20% PDMS in decalin), and a polystyrene-co-acrylate organic additive (0.005 g, approximately 1 wt% PAA). The mixture was stirred at room temperature at 700 rpm for 15 minutes, then heated to 145°C over 30 minutes, and maintained at 145°C for 3 hours. The resulting polyimide microparticles were filtered using a Buchner funnel, washed with acetone, and dried overnight at 80°C.

[0201] Using infrared spectroscopy, 1560 cm -1 and 1698cm -1 The disappearance of the peak at 2400cm -1 ~3300cm -1 The disappearance of the broad peak at 1698 cm (evidence of the absence of a deprotonated carboxylic acid functional group), and the absence of a broad peak at 1698 cm. -1 and 1768cm -1 The appearance of two distinct peaks (evidence of the presence of an imide functional group) confirms the complete imidation of PAA to polyimide.

[0202] Figure 3 shows differential scanning calorimetry (DSC) analysis of polyimide microparticles, indicating that the polymer has a melting point of 306°C and a crystallization temperature of 280°C, with a sufficiently wide sintering window of 26°C for successful SLS additive manufacturing. Furthermore, the DSC analysis confirms that the polyimide microparticles possess thermoplastic and semi-crystalline behavior not typically observed or expected in polyimides.

[0203] Based on thermogravimetric analysis (TGA), the decomposition temperature of the polyimide nanoparticles was 466°C. This indicates high thermal stability.

[0204] Figure 4 is an optical microscope image of the obtained polyimide microparticles. Figures 5A to 5C are scanning electron microscope (SEM) images of the obtained polyimide microparticles. The images show polyimide microparticles of similar size. Figures 5B and 5C show the intrinsic morphology of the polyimide microparticles. The surface has a porous, irregular skeleton (e.g., ribbon or flake) of thinner polymer structures. As shown in further examples, this structure is consistent throughout the polyimide microparticles.

[0205] The sample appears to contain many particles with a particle size ranging from approximately 10 micrometers to approximately 50 micrometers. These polyimide microparticles appear to have a particle size range suitable for SLS additive manufacturing.

[0206] Example 3 - Polycondensation Step: Using the same grade of materials, the procedure described in the polycondensation step of Example 1 was carried out in a 1 L round-bottom flask with 1,12-diaminododecane (22.780 g), 1-methyl-2-pyrrolidinone (250 g), and pyromellitic dianhydride (24.799 g).

[0207] Example 4 - Emulsion sol-gelimidization step: Using materials of the same grade, the procedure described in the emulsion sol-gelimidization step of Example 2 was carried out in a 250 mL round-bottom flask using a DMF solution of PAA (total 4.66 g, 20% PAA in DMF), a decalin solution of PDMS (10k cSt PDMS, total 23.3 g, 20% PDMS in decalin), and a polystyrene-co-acrylate organic additive (0.1 g).

[0208] Figure 6 is an optical microscope image of the obtained polyimide microparticles. Figures 7A and 7B are SEM images of the obtained polyimide microparticles. The images show polyimide microparticles of similar size. Figure 7B shows the intrinsic morphology of the polyimide microparticles, as well as the polystyrene-co-acrylate-based organic additive coating a portion of the surface of the polyimide microparticles. The surface has a porous, irregular skeleton (e.g., ribbons or flakes) with a thinner polymer structure. As shown in further examples, this structure is consistent throughout the polyimide microparticles.

[0209] Figure 8 shows a histogram obtained from light scattering of polyimide microparticles obtained in this embodiment. This histogram shows that many particles have a particle size of about 20 micrometers to about 80 micrometers. These polyimide microparticles appear to have a suitable particle size range for SLS additive manufacturing. Particle sieving may be useful to reduce the cluster of larger particle sizes and / or narrow the particle size span, thereby further increasing the suitability of the polyimide microparticles for SLS additive manufacturing.

[0210] Example 5 - A 250 mL three-necked round-bottom flask equipped with a magnetic stirrer and nitrogen inlet / outlet was filled with 1,12-diaminododecane (8.50 g, 98%, Sigma-Aldrich) followed by 165 mL of dry DMF by cannula transfer. The 1,12-diaminododecane was dissolved in the DMF while heating to approximately 40°C to 45°C under a nitrogen blanket. The mixture was stirred at 300 rpm while slowly adding pyromellitic dianhydride (9.32 g, 97%, Sigma-Aldrich, PMDA) to the flask in four equialiquots over 30 minutes. After the addition of PMDA was complete, the reaction mixture was refluxed at 155°C for 1.5 hours, then refluxed at ambient temperature overnight, and then refluxed again at 162°C for a further 3 hours the following day. The mixture was then cooled to 100°C, and a few drops of formic acid were added to the solution to dissolve all unreacted PMDA. Next, the reaction mixture was stirred for a further 2 hours. The resulting solution was cooled, the white solid was filtered, and thoroughly washed with formic acid and acetone. The white powder was then decanted from the formic acid / acetone mixture and re-slurried in acetone at ambient temperature for 2 hours. The final white powdery product was filtered and washed again with acetone and ether. The resulting wet cake was dried under vacuum at 80°C for 2 days to obtain a white polyimide powder in quantitative yield.

[0211] The crystallinity of the obtained polyimide microparticles was measured using DSC. The ΔH of the sample was 47.6 J / g. Using the 100% crystallinity standard (ΔH = 98 J / g) for polyimide R-BAPB based on 1,3-bis(3,3'-4,4'-dicarboxyphenoxy)benzene (dianhydride R) and 4,4'-bis(4-aminophenoxy)biphenyl (diamine BAPB), the crystallinity of the obtained polyimide microparticles was approximately 49%. This indicates that the polyimide microparticles produced by the method described herein contain semicrystalline polyimide.

[0212] Example 6 - A 100 mL three-necked round-bottom flask equipped with a magnetic stirrer and nitrogen inlet / outlet was filled with 1,8-diaminodooctane (1.07 g, 98%, Sigma-Aldrich) followed by 25 mL of dry DMF by cannula transfer. The 1,8-diaminooctane was dissolved in the DMF under a nitrogen blanket at ambient temperature. The mixture was stirred at 300 rpm while slowly adding pyromellitic dianhydride (1.62 g, 97%, Sigma-Aldrich, PMDA) to the flask in four equialiquots over 30 minutes. After the addition of PMDA was complete, the reaction mixture was stirred at ambient temperature for 30 minutes, then heated to 165°C and held for 3 hours. The resulting colloidal solution was cooled, and the white solid was filtered and thoroughly washed three times with formic acid and acetone using a centrifuge for separation and collection. The resulting wet cake was dried under vacuum at 80°C for 2 days to obtain a white polyimide powder in quantitative yield.

[0213] The crystallinity of the obtained polyimide microparticles was measured using DSC. The ΔH of the sample was 47.6 J / g. Using the criteria described in Example 5, the crystallinity of the obtained polyimide microparticles was approximately 54%. This indicates that the polyimide microparticles produced by the method described herein contain semicrystalline polyimide.

[0214] Example 7 - Polycondensation Step: Using materials of the same grade, the procedure described in the polycondensation step of Example 1 was carried out in a 1 L round-bottom flask with 1,12-diaminododecane (22.780 g), 1-methyl-2-pyrrolidinone (250 g), and pyromellitic dianhydride (24.799 g).

[0215] Using materials of the same grade, an emulsion sol-gelimidization step (the procedure described in the emulsion sol-gelimidization step of Example 2) was performed in a 250 mL round-bottom flask using a DMF solution of PAA (20.66 g from the polycondensation step above, 20% PAA in DMF), a decalin solution of PDMS (10k cSt PDMS, total 116.6 g, 20% PDMS in decalin), and a polystyrene-co-acrylate organic additive (0.2 g).

[0216] The mixture was stirred at room temperature at 620 rpm for 15 minutes, then heated to 140°C over 30 minutes, and maintained at 140°C for 3 hours. The resulting polyimide fine particles were filtered using a Buchner funnel, washed four times with heptane, and dried overnight at 80°C. The angle of repose of this material was 37.9 degrees, and it exhibited good flowability.

[0217] Figures 9A to 9C are SEM images of the obtained polyimide nanoparticles. The images show that these polyimide nanoparticles have a wider particle size span and lower roundness. However, as shown in Figures 9B to 9C, the surface morphology is less ribbon-like but a porous, irregular skeleton, more similar to a polymer molten material solidified into a porous structure. Figure 9C also shows the presence of polystyrene-co-acrylate-based organic additives on the surface of the polyimide nanoparticles.

[0218] Figures 10A to 10C are cross-sectional SEM images of the obtained polyimide microparticles. The polyimide microparticles were immobilized in epoxy, microtome-processed, and imaged. Figure 10A shows a single polyimide microparticle in which epoxy has partially permeated. The outer edge of the polyimide microparticle is indicated by arrow A, where the color transitions from dark gray to light gray. The portion of the polyimide microparticle infused with epoxy is indicated by arrow B. This indicates that the polyimide microparticles of this disclosure are porous. Figures 10B to 10C are higher-magnification SEM images of Figure 10A. These better show that the porous, irregular skeletal morphology extends throughout the polyimide microparticle, with arrow C indicating pores. Furthermore, arrow D indicates polystyrene-co-acrylate organic additive aggregates trapped within the polyimide microparticles during the synthesis process. Furthermore, arrow E indicates individual polystyrene-co-acrylate organic additives present on the surface of the porous, irregular skeletal structure inside the polyimide microparticles.

[0219] After sieving the polyimide particles obtained using a 300-micrometer sieve, the angle of repose was measured to be 38° (average of 3 measurements) at 23°C and 47% relative humidity. This is a suitable flow for use in SLS additive manufacturing. Note that a visual comparison of Example 7 with other previous examples shows that Example 7 appears to have lower roundness and a larger particle size span. Therefore, the previous examples are expected to have lower angles of repose and are thus more suitable for use in SLS additive manufacturing.

[0220] Accordingly, the present invention is well adapted to achieve the objectives and advantages described above, as well as the inherent advantages therein. The specific examples and configurations disclosed above are merely illustrative, as the present invention may be modified and implemented in different but equivalent ways that will be obvious to those skilled in the art and will benefit from the teachings herein. Furthermore, it is not intended to limit the present invention to any structural or design details other than those described in the following claims. Accordingly, the specific exemplary examples disclosed above may be modified, combined or altered, and it is clear that all such modifications will be considered within the scope and spirit of the present invention. The present invention as exemplary disclosed herein may be implemented in the absence of any elements not specifically disclosed herein and / or any optional elements disclosed herein. Compositions and methods are described using the terms “comprising,” “containing,” or “including” various components or processes, but compositions and methods may also “essentially consist of” or “consist of” various components and processes. All the number and scope disclosed above may vary somewhat. Whenever a numerical range with lower and upper limits is disclosed, any number and any range included within that range are specifically disclosed. In particular, all ranges of values ​​disclosed herein (in the form of “about a to about b,” or equally “approximately a to b,” or equally “about a to b”) should be understood to describe all numbers and ranges encompassed within a broad range of values. Furthermore, terms in the “Claims” have plain, ordinary meanings unless explicitly and clearly defined by the patent holder. In addition, when used in the “Claims,” the indefinite article “a” or “an” is defined herein to mean one or more of the elements it introduces.

Claims

1. 1. A method comprising: combining a diamine and a dianhydride in a first dry high boiling point solvent; reacting the diamine and the dianhydride to produce a mixture comprising poly(amic acid) (PAA) and the first dry high boiling solvent; emulsifying the mixture in a matrix fluid that is immiscible with the first dry high boiling point solvent using an emulsion stabilizer comprising nanoparticles or polystyrene-co-acrylate to form a precursor emulsion that is an oil-in-oil emulsion; and heating said precursor emulsion during and / or after formation to a temperature sufficient to polymerize said PAA to form polyimide particulates.

2. The diamines include ethylenediamine, propylenediamine, trimethylenediamine, diethylenetriamine, triethylenetetramine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, 1,12-dodecanediamine, 1,18-octadecanediamine, 3-methylheptamethylenediamine, 4,4-dimethylheptamethylenediamine, 4-methylnonamethylenediamine, 5-methylnonamethylenediamine, 2,5-dimethylhexamethylenediamine; 2,5-dimethylheptamethylenediamine; 2,2-dimethylpropylenediamine; N-methyl-bis(3-aminopropyl)amine; 3-methoxyhexamethylenediamine; 1,2-bis(3-aminopropoxy)ethane; bis(3-aminopropyl)sulfide; trans-1,4-cyclohexanediamine; bis-(4-aminocyclohexyl)methane; m-phenylenediamine; p-phenylenediamine; 2,4-diaminotoluene; 2,6-diaminotoluene; m-xylylenediamine; p-xylylenediamine; 2-Methyl-4,6-diethyl-1,3-phenylene-diamine; 5-methyl-4,6-diethyl-1,3-phenylenediamine; benzidine; 3,3''-Dimethylbenzidine; 3,3''-Dimethoxybenzidine; 1,5-Diaminonaphthalene; Bis(4-aminophenyl)methane; Bis(2-chloro-4-amino-3,5-diethylphenyl)methane; Bis(4-aminophenyl)propane; 2,4-Bis(b-amino-t-butyl)toluene; Bis(p-b-amino-t-butylphenyl)ether; Bis(p-b-methyl-o-aminophenyl)benzene; Bis(p-b-methyl-o-aminopentyl)benzene; 1,3-diamino-4-isopropylbenzene; bis(4-aminophenyl)sulfide; Bis(4-aminophenyl)sulfone; Bis(4-aminophenyl)ether; 1,3-bis(3-aminopropyl)tetramethyldisiloxane; 2,3,5,6-Tetramethyl-1,4-phenylenediamine; 2,6-Diaminotriptycene; 4,4'-Oxydianiline; 3,4'-Oxydianiline; 4,4'-Diaminodiphenylsulfone; 2,5-Dimethyl-1,4-phenylenediamine; 4,4'-Methylenedianiline; 5-Amino-2-(4-aminobenzene)benzimidazole; 2,2'-Dimethylbenzidine; 4,4'-Diaminobenzanilide; 2,2'-Bis(trifluoromethyl)benzidine; 2,2-Bis(3-amino-4-hydroxyphenyl)hexafluoro Fluoropropane; 1R,2R-diaminocyclohexane; 1,3-diaminoadamantane; Bis(aminomethyl)bicyclo[2.2.1]heptane; 5-tert-butyldimethylsilylamino-N-tert-butyldimethylsilyl-1,3,3-trimethylcyclohexaneethylamine; 2,5-diamino-2,5-dideoxy-1,4:3,6-dianhydroiditol; 2,5-diamino-2,5-dideoxy-1,4:3,6-dianhydrosorbitol; N,N-bis(3-aminopropyl)-methylamine; Ethylenediamine; 1,3-Diaminopropane; 1,4-Diaminobutane; 1,6-Diaminohexane; Poly(propylene glycol) bis(2-aminopropyl ether); 2,2'-Dimethyl-4,4'-diaminodicyclohexylmethane; 2,2'-Bis(trifluoromethyl)-4,4'-diaminobicyclohexylmethane; 4,4'-Methylenebis(cyclohexylamine); 4,4'-Hexafluoroisopropylidenebis(cyclohexylamine); 4,4'-Methylenebis(2-methylcyclohexylamine) cyclohexylamine); bis(4-amino-3-ethylcyclohexyl)methane; 3,3'-diamino-1,1'-diadamantane; trans-11,12-diamino-9,10-dihydro-9,10-ethanoanthracene; 4,4'-diaminodiphenylethane; 4,4'-(cyclohexane-1,4-diylbis(sulfanediyl))dianiline; 1,4-bis[2-amino-4-(trifluoromethyl)phenyl]piperazine; 4,4'-diamino-α-truxillate dimethyl ,4',4''-[(perfluorocyclobutane-1,2-diyl)bis(oxy)]bis((1,1'-biphenyl)-4-amine); 5,5'-isopropylidenebis(2-furfurylamine); 1,1-bis(4-aminophenyl)cyclohexane; 1,1-bis(4-aminophenyl)-4-methylcyclohexane; 1,1-bis(4-aminophenyl)-3,3,5-trimethylcyclohexane; 2,2-bis(4-aminophenyl)norbornane; 1,1-bis[4-(2- trifluoromethyl-4-amino-phenoxy)phenyl]-4-tert-butylcyclohexane; 3,3-bis(4-aminophenyl)quinacridine; (+)-cis-1,3-bis(4-amino-2-(trifluoromethyl)phenoxymethylene)-1,2,2-trimethylcyclopentane; 1,3-bis(4-aminophenoxymethylene)-1,2,2-trimethylcyclopentane; 1,4:3,6-dianhydro-2,5-di-O-(4-aminophenyl)-D-mannitol; 1,4:3,6-dianhydro-2,5-di-O-(4-aminophenyl)-D-sorbitol; 2,5-bis(2-trifluoromethyl-4-aminophenoxy)-1,4:3,6-dianhydrosorbitol; 2,5-bis(2-methyl-4-amino-phenoxy)-1,4:3,6-dianhydrosorbitol; 1,6-bis(4-aminophenyl)adamantane; 4,9-bis(4-aminophenyl)adamantane; (5R,11R)-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocin-2,8 -diamines; (5S,11S)-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocin-2,8-diamine; 4,10-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocin-2,8-diamine; 4,10-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocin-3,9-diamine; 2,8-dibromo-1,4,7,10-tetramethyl-3,9-diamino-6,12-dihydro-5,11-methanodibenzo[b,f][1,5]diazocin; 2,4,8,10-tetramethyl-1,7-diamino-6,12-dihydro-5,11-methanodibenzo[b,f][1,5]diazocin; 2,8-diamino-1,3,7,9-tetramethyl-6H,12H-5,11-methanodibenzo-[b,f][1,5]diazocin; 1,7-diamino-6H,12H-5,11-methanodibenzo[1,5]diazocin-2,8- Diol; 3,3,3',3'-tetramethyl-1,1'-spirobisindane-5,5'-diamino-6,6'-diol, 5(6),5'(6')-diamino-3,3,3',3'-tetramethyl-1,1'-spirobisindane; 6,6'-bis-[2''-trifluoromethyl-4''-(4'''-aminophenyl)phenoxy]-3,3,3',3'-tetra Methyl-1,1'-spirobiindane; 4,4'-((3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobi[indene]-6,6'-diyl)bis(oxy))bis(2-methoxyaniline); 3,3,3',3'-tetramethyl-2,2',3,3'-tetrahydro-1,1'-spirobi[cyclopenta[b]phenazine] 1-(4-aminophenyl)-5(6)-aminoindan; 4'-[4-[6-[[4'-amino-3-(trifluoromethyl)[1,1'-biphenyl]-4-yl]oxy]-2,3-dihydro-1,3,3-trimethyl-1H-inden-1-yl]phenoxy]-3'-(trifluoromethyl)-[1,1'-biphenyl]-4-amine; 2,6(7)-diamino-9,10-dimethyl-9,10-dihydro-9,10-ethanoanthracene; 2,8-dimethyl-3,9-diamino-5,6,11,12-tetrahydro-5,11-methanodibenzo[a,e][8]annulene; spiro-(adamantane-2,9'(2',7'-diamino)-fluorene), 2,2-bis(3-amino-4-hydroxyphenyl)adamantine; 2,2-bis(4-aminophenyl)adamantane; 1,3-bis[4-(4-aminophenoxy)phenyl]adamantane; trans-di(aminobenzo)-18-crown-6,2,2'-dimethyl-4,4'-diamino-biphenyl, 4,9-dioxa-1,12-dodecanediamine; 4,7,10-trioxa-1,13-tridecanediamine; and any combination thereof.

3. The dianhydrides include pyromellitic dianhydride, 2,2-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl ether dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone dianhydride; 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride; 2,2-bis(4-(2,3-dicarboxyphenoxy)phenyl)propane dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenyl ether dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)benzophenone dianhydride; 4,4'-bis(2,3-dicarboxyphenoxy)diphenylsulfone dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenyl-2,2-propane dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenyl ether dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)benzophenone dianhydride; 4-(2,3-dicarboxyphenoxy)-4'-(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride; 1,2,4,5-benzenetetracarboxylic dianhydride; 1S,2R,4S,5R-cyclohexanetetracarboxylic dianhydride; 1S,2S,4R,5R-cyclohexanetetracarboxylic dianhydride; 1R,2S,4S,5R-cyclohexanetetracarboxylic dianhydride; bicyclo[2.2.2]octane-2-endo,3-endo,5-exo,6-exo-tetracarboxylic acid 2,3:5,6-dianhydride; bicyclo chloro[2.2.2]octane-2-exo,3-exo,5-exo,6-exo-2,3:5,6-dianhydride; cis-1,2,3,4-cyclohexanetetracarboxylic acid dianhydride; trans-1,2,3,4-cyclohexanetetracarboxylic acid dianhydride; bicyclo[2.2.1]heptane-2-endo,3-endo,5-exo,6-exo-tetracarboxylic acid 2:3,5:6-dianhydride; bicyclo[2.

2. l]heptane-2-exo,3-exo,5-exo,6-exo-tetracarboxylic acid 2:3,5:6-dianhydride; (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethano-naphthalene-2c,3c,6c,7c-tetracarboxylic acid 2,3:6,7-dianhydride; (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethano-naphthalene-2t,3t,6c,7c-tetracarboxylic acid 2,3:6, 7-dianhydride; rel[1S,5R,6R]-3-oxabicyclo[3.2.1]octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), bicyclo[2.2.1]heptane-2-exo,3-exo,5-exo-tricarboxyl-5-endo-acetic dianhydride; bicyclo[2.2.1]heptane-2-exo,3-exo,5-endo-tricarboxyl-5-exo-acetic anhydride; 1,2,3,4-Cyclobutanetetracarboxylic dianhydride; butane-1,2,3,4-tetracarboxylic dianhydride; bicyclo-[2.2.2]oct-7-ene-2-exo,3-exo,5-exo,6-exo-2,3:5,6-dianhydride; 1,8-Dimethylbicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride; Bicyclo[4.2.0]octane-3,4,7,8-tetracarboxylic dianhydride; Bicyclo[4.2.0]octane-3,4,7,8-tetracarboxylic dianhydride; rel-(1R,1'S,3R,3'S,4S,4'R)-dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride; rel-(1R,1'S,3R,3'S,4R,4'S)-dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride; dicyclohexyl-1R,1'S,2S,2R',3R ,3S'-tetracarboxylic dianhydride; dicyclohexyl-2,3',3,4'-tetracarboxylic dianhydride; 5,5'-oxybis(hexahydro-1,3-isobenzofurandione); 5,5'-(1-methylethylidene)bis[hexahydro-1,3-isobenzofurandione]; 5,5'-methylenebis(hexahydro-1,3-isobenzofurandione); 5,5'-carbonylbis(hexahydroisobenzofuran-1,3-dione); 1,2,3,4-cyclopentanetetracarboxylic dianhydride; 1,2-bis(4'-oxa-3',5-dioxotricyclo-[4.3.0.1 2,5 ]decan-8'-yloxy)ethane; 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride; 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, norbornane-2-spiro-α-cyclohexanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic dianhydride; cyclopentanone bisspiro-norbornanetetracarboxylic dianhydride; 1,2,4-Cyclopentanetricarboxylic acid-3-(carboxymethyl)-1,4:2,3-dianhydride; 3,3'-(1,4-piperazinediyl)bis[dihydro-2,5-furandione]; bicyclo[2.2.1]-heptane-2-methanecarboxyl-3,5,6-tricarboxyl-2,3:5,6-dianhydride; 2R,5R,7S,10S-naphthanetetracarboxylic dianhydride; pentacyclo[8.2.1.1 4’7 0 2’9 0 3’8 ]tetradecane-5,6,11,12-tetracarboxylic dianhydride; tricyclo[4.2.2.02,5]dec-7-ene-3,4,9,10-tetracarboxylic dianhydride; dodecahydro-1H-4,11:5,9-dimethanofluorene[2,3-c:6,7-c']difuran-1,3,6,8(3aH)-tetraone; tetradecahydro-4,10:5,9-dimethanonaphtho[2'',3'':3,4;6'',7'':3',4']dicyclobuta[1,2-c:1',2'-c']difuran-1,3,6,8-tetrone, 1,2,3,4-butanetetracarboxylic dianhydride; 5,5'-thiobis[hexahydro-4,7-methanoisobenzofuran-1,3-dione]; 1,1,2,2-ethanetetracarboxylic dianhydride; 2. The method of claim 1, wherein the anhydride is selected from the group consisting of 5,5'-sulfonylbis(hexahydro-4,7-ethanoisobenzofuran-1,3-dione); 5R,5'R-5,5'-exo-(1,1,3,3,5,5-hexamethyltrisiloxane-1,5-diyl)bisbicyclo[2.2.1]heptane-endo-2,3-dicarboxylic anhydride; 5S,5'S-5,5'-exo-(1,1,3,3,5,5-hexamethyltrisiloxane-1,5-diyl)bisbicyclo[2.2.1]heptane-endo-2,3-dicarboxylic anhydride; and any combination thereof.

4. 10. The method of claim 1, wherein the diamine and the dianhydride are reacted at about 40° C. or less.

5. The method of claim 1, wherein the diamine and the dianhydride are reacted for about 6 hours to about 48 hours.

6. 2. The method of claim 1, wherein the stoichiometric ratio of the diamine to the dianhydride is from about 2:1 to about 1:

2.

7. The reaction of the diamine with the dianhydride is dissolving the diamine in the first dry high boiling point solvent; adding said dianhydride to said first dry high boiling solvent having said diamine dissolved therein.

8. The method of claim 1 , wherein the emulsion stabilizer is present as a coating on the surface of the polyimide particulates.

9. 10. The method of claim 1, wherein the temperature sufficient to polymerize the PAA is from about 100°C to about 250°C.

10. washing the polyimide microparticles; The method of claim 1 , further comprising drying the polyimide particulates after washing.

11. The method of claim 1 , wherein the polyimide particulate has an angle of repose of about 25° to about 45°.

12. 10. The composition of claim 1, wherein the polyimide particulate has a sintering window of about 15°C to about 35°C.

13. 1. A method comprising: combining a diamine and a dianhydride in a first dry high boiling point solvent; reacting the diamine and the dianhydride to produce a mixture comprising poly(amic acid) (PAA) and the first dry high boiling solvent; Extracting the PAA from the mixture; and dissolving the PAA in a second dry high boiling point solvent to produce a PAA solution; emulsifying the PAA solution in a matrix fluid that is immiscible with the second dry high boiling point solvent using an emulsion stabilizer to form a precursor emulsion that is an oil-in-oil emulsion; and heating said precursor emulsion during and / or after formation to a temperature sufficient to polymerize said PAA to form polyimide particulates.

14. 14. The method of claim 13, wherein the diamine and the dianhydride are reacted at about 40° C. or less.

15. The method of claim 13, wherein the diamine and the dianhydride are reacted for about 6 hours to about 48 hours.

16. The method of claim 13, wherein the stoichiometric ratio of the diamine to the dianhydride is from about 2:1 to about 1:

2.

17. The method of claim 13 , wherein the emulsion stabilizer is present as a coating on the surface of the polyimide particulates.

18. The method of claim 13, wherein the temperature sufficient to polymerize the PAA is from about 100°C to about 250°C.

19. A composition comprising: i) polyimide microparticles comprising: i) polyimide; and ii) nanoparticles or polystyrene-co-acrylate, wherein the polyimide microparticles have a porous irregular skeletal morphology comprising: (a) a flake-like structure; (b) a ribbon-like structure; and / or an interconnected solidified polymer melt structure.

20. The method of claim 13, wherein the emulsion stabilizer comprises nanoparticles or polystyrene-co-acrylate.